Resin composition, laminated sheet, prepreg, cured product, substrate with cured product, and electronic device

A resin composition with polyimide resin and a thermally conductive filler addresses embedding and plating resistance issues, providing superior substrate processing and long-term heat resistance.

JP7601263B2Active Publication Date: 2024-12-17TOYO INK MFG CO LTD
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
JP2023570838
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-12-15
Publication Date
2024-12-17
Estimated Expiration
2042-12-15

AI Technical Summary

Technical Problem

Existing resin compositions for electronic components fail to provide excellent suitability for substrate processing, especially in embedding into uneven shapes, plating solution resistance, and heat cycle resistance, while also requiring high bending strength and long-term heat resistance.

Method used

A resin composition containing a polyimide resin with residues from dimer diamine and/or dimer diisocyanate, a curable compound, and a thermally conductive filler, with specific functional group limitations and molecular weight ranges, to enhance embedding, plating solution resistance, and heat cycle resistance.

Benefits of technology

The resin composition exhibits excellent suitability for substrate processing, including embedding into irregularities, plating solution resistance, and heat cycle resistance, with cured products demonstrating high bending strength and long-term heat resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601263000001
    Figure 0007601263000001
  • Figure 0007601263000002
    Figure 0007601263000002
  • Figure 0007601263000003
    Figure 0007601263000003
Patent Text Reader

Abstract

The present invention provides a resin composition which has substrate processing adequacy including embeddability into substrate relief patterns, heat cycle resistance and plating solution resistance, and which enables the achievement of a cured product that has excellent long-term heat resistance and excellent bending strength. The above is achieved by means of a resin composition which contains a polyimide resin (A), a curable compound (B) and a thermally conductive filler (C), wherein: a cured product of this resin composition has a Tg of 140°C to 400°C; the polyimide resin (A) has a residue X2d that is derived from a dimer diamine and / or a dimer diisocyanate, while having a total average number of functional groups selected from among an amino group, an acid anhydride group and a maleimide group of 1 or less (including 0); the temperature and Mw at which the storage elastic modulus G' of the polyimide resin (A) is 1.0 × 107 Pa are within specific ranges; and the curable compound (B) is selected from the group consisting of an epoxy compound (b1) and the like.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a resin composition, a laminate sheet, and a prepreg. The present disclosure further relates to a cured product obtained from the resin composition, a substrate with the cured product formed by curing the resin composition, and an electronic device equipped with the substrate with the cured product. [Background technology]

[0002] In electronic components, members obtained by curing a resin composition are used in various parts. For example, in a multilayer printed wiring board, an interlayer insulating layer is formed between a plurality of conductor layers. In addition, a prepreg in which a resin composition is impregnated into a glass cloth or the like is used as an insulating layer that covers the conductor layer of a printed wiring board. Insulating sealing resins are also used in semiconductor packages.

[0003] As such a resin composition, a composition containing a resin component, a curing component, and an inorganic filler component is disclosed. For example, Patent Document 1 discloses a composition containing an epoxy compound, a curing agent, silica, and a polyimide having a dimer structure, and Patent Document 2 discloses a composition containing a specific amount of an N-alkyl bismaleimide compound having a skeleton derived from a dimer diamine, an epoxy compound, an inorganic filler, and a specific curing agent. Patent Document 3 discloses a resin composition containing a thermosetting resin, an inorganic filler, a specific amount of an organic filler, and an adhesive softener. Furthermore, Patent Document 4 discloses a resin composition for forming an insulating layer containing a specific amount of an epoxy resin, a specific amount of a maleimide compound having a specific structure, a specific amount of an active ester compound, and an inorganic filler.

[0004] Patent Document 5 discloses a polyimide-based adhesive composition containing a polyimide resin obtained by reacting aromatic tetracarboxylic acids and diamines containing a specific amount of dimer diamine, a thermosetting resin, a flame retardant, and an organic solvent. Patent Document 6 discloses a resin material containing a cyclohexane ring, a maleimide compound having a dimer structure, a polyimide resin having a dimer structure, an epoxy compound, an active ester compound, and an inorganic filler. Patent Document 7 discloses a resin composition containing a thermosetting resin, an inorganic filler, a specific amount of an organic filler, and an adhesive softener. Patent Document 8 discloses a polyimide-based adhesive containing a terminal-modified polyimide, a crosslinking agent, and an organic solvent, with the objective of providing a polyimide-based adhesive that provides an adhesive layer having a low loss modulus in the B stage, good heat-resistant adhesion, and good low dielectric properties. Patent Document 8 discloses a polyimide-based adhesive containing a terminal-modified polyimide, a crosslinking agent, and an organic solvent, with the objective of providing a polyimide-based adhesive that provides an adhesive layer having a low loss modulus in the B stage, good heat-resistant adhesion, and good low dielectric properties. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2018 / 062404 [Patent Document 2] International Publication No. 2019 / 189466 [Patent Document 3] JP 2020-158704 A [Patent Document 4] JP 2020-186392 A [Patent Document 5] JP 2013-199645 A [Patent Document 6] Patent Publication No. 2021-25052 [Patent Document 7] JP 2020-158704 A [Patent Document 8] JP 2016-191049 A Summary of the Invention [Problem to be solved by the invention]

[0006] With the advancement of high functionality in electronic devices, there is an increasing demand for high reliability in electronic components built into the devices. In the case of resin compositions, materials with excellent substrate processing suitability are required when manufacturing printed wiring boards and the like. Specifically, when forming an insulating layer made of a resin composition on a substrate on which a concave-convex pattern such as wiring is formed, materials with excellent embedding properties for the concave-convex shape are required. In addition, cured products obtained by curing the resin compositions are required to have excellent plating resistance (alkali resistance, acid resistance). Furthermore, materials with heat cycle resistance that can withstand high-temperature processes such as solder reflow processes are required. In addition, there is a demand in the market for materials that combine long-term heat resistance and bending strength.

[0007] The present disclosure has been made in view of the above background, and has an object to provide a resin composition that has substrate processability, including the ability to embed into substrate irregularities, plating solution resistance, and heat cycle resistance, and that produces a cured product that has excellent long-term heat resistance and bending strength, as well as a laminate sheet, a prepreg, a cured product, a substrate with the cured product, and an electronic device, which are formed using the resin composition. [Means for solving the problem]

[0008] As a result of extensive investigations, the present inventors have found that the problems of the present disclosure can be solved in the following aspect, and have thus completed the present disclosure. [1]: A resin composition comprising a polyimide resin (A), a curable compound (B) and a thermally conductive filler (C), The polyimide resin (A) contains a residue X derived from dimer diamine and / or dimer diisocyanate. 2 d, the total average number of functional groups selected from an amino group, an acid anhydride group, and a maleimide group is 1 or less, inclusive of 0, The storage modulus G' of polyimide resin (A) is 1.0×10 7the temperature at which the molecular weight V is 1.0 Pa is in the range of −30 to 90° C., and the weight average molecular weight of the polyimide resin (A) is 10,000 to 100,000; the curable compound (B) is one or more selected from the group consisting of an epoxy compound (b1), a cyanate ester compound (b2), a maleimide compound (b3), a polyphenylene ether compound (b4) and a nadimide compound (b5); A resin composition having a glass transition temperature of 140 to 400°C after curing. [2]: Polyimide resin (A) is represented by the general formula (1): [ka] (X 1 is independently a tetravalent tetracarboxylic acid residue for each repeating unit, and X 2 is a divalent organic group for each repeating unit, 1 and imide bonds are bonded together to form two imide rings.) The repeating unit has a structure represented by The X constituting the polyimide resin (A) 2 When the whole is taken as 100 mol %, the residue X derived from the dimer diamine and / or dimer diisocyanate is 2 The resin composition according to [1], characterized in that d is 60 to 100 mol %. [3]: The resin composition according to [1] or [2], further comprising a heat stabilizer (D). [4]: The resin composition according to any one of [1] to [3], characterized in that the polyimide resin (A) is blended in an amount of 1 to 40 mass% based on 100 mass% of the non-volatile components of the resin composition. [5]: The resin composition according to any one of [1] to [4], comprising an epoxy compound (b1) as the curable compound (B) and further comprising an active ester compound. [6]: A laminate sheet comprising a substrate and a resin composition layer formed on the substrate from the resin composition according to any one of [1] to [5]. [7]: A prepreg obtained by impregnating a substrate with the resin composition according to any one of [1] to [5]. [8]: A cured product obtained from the resin composition according to any one of [1] to [5]. [9]: A substrate with a cured product, comprising a cured product formed by curing the resin composition according to any one of [1] to [5].

[10] : An electronic device equipped with a substrate with the cured product described in [9]. Effect of the Invention

[0009] The present disclosure has the excellent effect of providing a resin composition that has excellent suitability for substrate processing (ability to embed into substrate irregularities, heat cycle resistance, and plating solution resistance) and that provides a cured product that has excellent long-term heat resistance and bending strength, as well as a laminate sheet, a prepreg, a cured product, a substrate with the cured product, and an electronic device that are formed using the resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present disclosure will be described in detail below. Needless to say, other embodiments are also included in the scope of the present disclosure as long as they are consistent with the gist of the present disclosure. In addition, in this specification, a numerical range specified using "~" includes the numerical values ​​written before and after "~" as the range of the lower and upper limits. In this specification, "film" and "sheet" are synonymous and are not distinguished by thickness. In addition, unless otherwise noted, the various components appearing in this specification may be used independently alone or in combination of two or more types. The numerical values ​​described in this specification refer to values ​​obtained by the method described in [Examples] below.

[0011] 1.Resin composition The resin composition according to this embodiment (hereinafter also referred to as the present composition) contains a polyimide resin (A), a curable compound (B) and a thermally conductive filler (C). The polyimide resin (A) contains a residue X derived from a dimer diamine and / or a dimer diisocyanate. 2d (hereinafter also referred to as a dimer structure). The polyimide resin (A) has an average total number of functional groups selected from amino groups, acid anhydride groups, and maleimide groups of 1 or less, including 0. The storage modulus G' of the polyimide resin (A) is 1.0×10 7 The temperature at which the viscosity becomes 0.1 Pa is within a range from −30° C. to 90° C., and the weight average molecular weight (hereinafter also referred to as Mw) is within a range from 10,000 to 100,000. The polyimide resin (A) can be used alone or in combination of two or more kinds.

[0012] The curable compound (B) is one or more selected from the group consisting of epoxy compounds (b1), cyanate ester compounds (b2), maleimide compounds (b3), polyphenylene ether compounds (b4) and nadimide compounds (b5) (hereinafter also referred to as (b1) to (b5)). The composition has a glass transition temperature (hereinafter also referred to as Tg) of 140 to 400°C of the cured product obtained by the curing treatment.

[0013] The average number of functional groups is the total average number of functional groups selected from amino groups, acid anhydride groups, and maleimide groups per molecule of polyimide resin (A), and can be determined from the charging ratio of raw material components used in the synthesis of polyimide resin (A). The total average number of functional groups being 0 means that polyimide resin (A) has no amino groups, acid anhydride groups, or maleimide groups. The total average number of functional groups being 1 or less means that the total number of functional groups, amino groups, acid anhydride groups, and maleimide groups, is 1 or less on average in one molecule of polyimide resin (A).

[0014] In this specification, the term "cured product" refers to a product cured by forming a three-dimensional crosslinked structure through a curing treatment, and refers to a state in which the product is cured to such an extent that the curing reaction does not proceed substantially even if the product is cured further. The curing treatment may include a form in which the curable compounds (B) crosslink with each other, a form in which the curable compound (B) crosslinks with the polyimide resin (A), a form in which the curable compound (B) crosslinks with other components, and a form in which these are combined in any manner. Examples of the curing treatment include a heat curing treatment and a photocuring treatment. When a thermally reactive group is used, a heating treatment is usually performed, and when a photoreactive group is used, a photoirradiation treatment is usually performed. Although the curing conditions vary depending on the composition, when a thermally reactive group is used, a cured product can be obtained by, for example, treating at 180°C for about 60 minutes. Similarly, when a photoreactive group is used, a cured product can be obtained by, for example, irradiating the composition with an actinic ray (e.g., 365 nm) at a light amount that sufficiently proceeds with the crosslinking reaction. Note that when the present composition is molded into a desired shape such as a sheet, a state in which a part of the composition may undergo a curing reaction, but which can be cured by further curing treatment, is not included in the cured product referred to here. At the stage of the resin composition, some of the components may be in a semi-cured B-stage state.

[0015] Since the composition has the above-mentioned structure, it is possible to provide a resin composition having excellent embedding ability into uneven surfaces of a substrate, excellent heat cycle resistance and plating solution resistance in a substrate processing process, and high suitability for substrate processing. The main reason for this is believed to be that the polyimide resin (A) having high flexibility and Mw in a specific range is blended into the blending components of the resin composition that have a relatively high glass transition temperature when cured, and the polyimide resin (A) has an average total functional group number of amino groups, acid anhydride groups and maleimide groups of 1 or less, including 0, thereby increasing the fluidity before curing and bringing out a stress relaxation effect after curing.

[0016] In addition, since the composition has the above-mentioned structure, the cured product has excellent long-term heat resistance. The main reason for this is believed to be that the thermally conductive filler (C) is added as a compounding component of the resin composition that results in a relatively high glass transition temperature when cured, and further, the polyimide resin (A) of the above-mentioned structure that has a dimer structure and imide groups with high planarity and excellent heat resistance is combined.

[0017] Furthermore, since the composition has the above-mentioned structure, the bending strength of the cured product is excellent. The main reason is believed to be that the resin composition has a relatively high glass transition temperature when cured, and is blended with a polyimide resin (A) having a dimer structure with a hydrocarbon chain or a ring structure, with little interaction between molecular chains, and moderate flexibility (having a storage modulus in the above-mentioned specific range), and further having an Mw in the above-mentioned specific range. By blending such a polyimide resin (A) with a curable compound (B) that becomes rigid upon curing, stress relaxation properties are imparted to the cured product, and fracture toughness is imparted to the composition blended with the curable compound (B) and the thermally conductive filler (C). The components of the composition and the manufacturing method thereof will be described in detail below.

[0018] 1-1. Polyimide resin (A) The polyimide resin (A) contains a residue X derived from dimer diamine and / or dimer diisocyanate. 2 d. The polyimide resin (A) has an average total number of functional groups selected from amino groups, acid anhydride groups, and maleimide groups of 1 or less, including 0. The polyimide resin (A) has a storage modulus G' of 1.0×10 7 The temperature at which it becomes Pa is in the range of -30 to 90°C, and Mw is in the range of 10,000 to 100,000.

[0019] Dimer diamine can be obtained, for example, by converting the carboxy group of a dimer acid to an amino group. Dimer diisocyanate can be obtained, for example, by converting the carboxy group of a dimer acid to an isocyanate group. Here, the dimer acid refers to a dimer of an unsaturated aliphatic carboxylic acid or a hydrogenated product thereof. For example, dimer acids can be obtained by dimerizing natural fatty acids such as soybean oil fatty acids, tall oil fatty acids, and rapeseed oil fatty acids, or unsaturated fatty acids such as linoleic acid, linoleic acid, oleic acid, erucic acid, myristoleic acid, palmitoleic acid, sapienic acid, elaidic acid, stearolic acid, vaccenic acid, gadoleic acid, eicosenoic acid, brassidic acid, nervonic acid, eicosadienoic acid, docosadienoic acid, pinoleic acid, eleostearic acid, mead acid, dihomo-γ-linolenic acid, eicosatrienoic acid, stearidonic acid, arachidonic acid, eicosatetraenoic acid, cetoleic acid, adrenic acid, bosseopentaenoic acid, osbondoic acid, sardine acid, tetracosapentaenoic acid, eicosapentaenoic acid, docosahexaenoic acid, and herring acid. The unsaturated bonds may be hydrogenated as necessary to reduce the degree of unsaturation. Dimer diamines and dimer diisocyanates with a reduced degree of unsaturation are suitable in terms of oxidation resistance (particularly coloration at high temperatures) and suppression of gelation during synthesis.

[0020] The dimer acid is preferably a compound having 20 to 60 carbon atoms, more preferably a compound having 24 to 56 carbon atoms, even more preferably a compound having 28 to 48 carbon atoms, and even more preferably a compound having 36 to 44 carbon atoms. A dicarboxylic acid compound having a branched structure obtained by Diels-Alder reaction of a fatty acid is preferred. The branched structure is preferably an aliphatic chain or a ring structure, more preferably a ring structure. The ring structure is preferably one or more aromatic rings or an alicyclic structure, more preferably an alicyclic structure. When there are two ring structures, the two rings may be independent or continuous. One or more types of dimer diamine and dimer diisocyanate compounds can be used. The alicyclic structure may have one or more double bonds in the ring, or may have no double bond. A method for converting the carboxy group of the dimer acid to an amino group includes, for example, a method of amidating the carboxylic acid, converting it to an amine by Hofmann rearrangement, and further distilling and purifying it. The carboxy group of the dimer acid can be converted to a diisocyanate group, for example, by converting a carboxylic acid into an isocyanate group through Curtius rearrangement.

[0021] The amino group in the dimer diamine or the isocyanate group in the dimer diisocyanate may be directly bonded to the ring structure, but from the viewpoint of improving solubility and flexibility, it is preferable that the amino group is bonded to the ring structure via an aliphatic chain. The number of carbon atoms between the amino group or the isocyanate group and the ring structure is preferably 2 to 25. A suitable example of the aliphatic chain is a chain-like hydrocarbon group such as an alkylene group. A suitable example is a compound in which the two amino groups or isocyanate groups are each bonded to a ring structure via an alkylene group.

[0022] Specific examples of dimer acids (polybasic acids) for obtaining dimer diamine or dimer diisocyanate include the following chemical formulas (d1) to (d4). These are just examples, and the dimer acid is not limited to the following structures.

[0023] [ka]

[0024] The dimer diamine and dimer diisocyanate are preferably compounds having 20 to 60 carbon atoms, more preferably compounds having 24 to 56 carbon atoms, even more preferably compounds having 28 to 48 carbon atoms, and still more preferably compounds having 36 to 44 carbon atoms. Such carbon numbers are preferred from the viewpoint of ease of availability.

[0025] Commercially available dimer diamine products include, for example, "Priamine 1071", "Priamine 1073", "Priamine 1074", and "Priamine 1075" manufactured by Croda Japan, and "Versamin 551" manufactured by BASF Japan.

[0026] As a result of intensive research by the present inventors, it was found that the substrate processing suitability can be improved by making the total number of functional groups of amino groups, acid anhydride groups, and maleimide groups in one molecule of polyimide resin (A) 1 or less on average. By making the total average number of functional groups of amino groups, acid anhydride groups, and maleimide groups in polyimide resin (A) 1 or less (including 0), it is possible to suppress a structure in which polyimide resin (A) is incorporated into a crosslinked structure via these groups. In other words, the number of bonds between polyimide resin (A) and curable compound (B) via these groups can be made one or less on average. As a result, the flowability is increased at the stage before the curing treatment, and the embedding ability into unevenness of circuit boards such as wiring formed on a substrate is excellent, while the stress relaxation property and dispersibility of polyimide resin (A) after the curing treatment are improved, and the plating solution resistance and long-term heat resistance of the cured product can be effectively improved. From the viewpoint of further improving the suitability for substrate processing, it is more preferable to include a carboxyl group in addition to an amino group, an acid anhydride group, and a maleimide group as groups that make the total average number of functional groups in one molecule of the polyimide resin (A) 1 or less (including 0). That is, it is more preferable that the total average number of functional groups selected from the amino group, the acid anhydride group, the carboxyl group, and the maleimide group is 1 or less, including 0. In this case, the average number of functional groups refers to the total average number of functional groups selected from the amino group, the acid anhydride group, the carboxyl group, and the maleimide group per molecule of the polyimide resin (A).

[0027] When an epoxy compound (b1) is used as the curable compound (B), the high reactivity of the epoxy group facilitates crosslinking formation at a stage before the curing treatment. According to the present composition, the total number of functional groups, such as amino groups, acid anhydride groups, and maleimide groups (hereinafter also referred to as amino groups, etc.), is set to 1 or less on average in one molecule of the polyimide resin (A), thereby suppressing the crosslinking reaction at a stage before the curing treatment, and effectively improving poor embedding of wiring and other circuit boards formed on a substrate into unevenness. On the other hand, when a cyanate ester compound (b2), a maleimide compound (b3), a polyphenylene ether compound (b4), and / or a nadiimide compound (b5), which are less reactive than the epoxy compound (b1), are used as the curable compound (B), the acid anhydride group, amino, etc. of the polyimide resin (A) tend to remain in the cured product after the curing treatment. According to the present composition, by controlling the total number of functional groups, namely, amino groups, acid anhydride groups, and maleimide groups, in one molecule of the polyimide resin (A) to an average of 1 or less, the number of amino groups remaining after curing can be reduced, resulting in excellent plating solution resistance such as acid resistance. Furthermore, according to the present composition, by controlling the number of functional groups of the maleimide groups to fall within the above range, it is possible to prevent the crosslink density around the crosslinked sites of the polyimide resin (A) from increasing, appropriately maintain the stress relaxation properties of the polyimide resin (A), and maintain good heat cycle resistance of the cured product.

[0028] Polyimide resin (A) has a storage modulus G' of 1.0 x 10 7 By setting the temperature within this range, a polyimide resin (A) having a high flexibility can be obtained. From the viewpoint of bending strength and long-term heat resistance, it is preferable that the temperature at which the storage modulus G' is 1.0×10 Pa is set within the range of 30 to 80° C. 7 It is more preferable that there is a temperature at which the storage modulus G' is 1.0 x 10 Pa at any temperature between 30 and 70°C. 7 It is further preferable that there is a temperature at which the temperature is 1 Pa.

[0029] By including the thermally conductive filler (C), a molded product with excellent heat dissipation properties can be obtained. On the other hand, although the occurrence of voids is not a significant problem when forming a coating film, when a prepreg is produced, the inclusion of the thermally conductive filler (C) makes voids more likely to occur. This problem becomes more likely as the temperature decreases and the content of the thermally conductive filler (C) increases. As a result of extensive investigations by the present inventors, it was found that the storage modulus G' of 1.0×10 7 It was found that by including a polyimide resin (A) having a temperature at which its elastic modulus becomes -30°C or higher and lower than 30°C, the occurrence of voids can be more effectively suppressed even when a prepreg is formed using a resin composition containing a thermally conductive filler (C). In other words, it is believed that by using a polyimide resin (A) having low elasticity in the low temperature range, voids can be effectively filled during prepreg production even at a relatively low drying temperature. From the viewpoint of lowering the drying temperature of the prepreg, it is preferable to use a polyimide resin (A) having a storage modulus G' of 1.0 x 10 7 The polyimide resin (A) preferably has a temperature at which the viscosity becomes Pa of -15°C or more and less than 27°C, and more preferably has a temperature at which the viscosity becomes Pa of -5°C or more and less than 27°C. The environmental load can be reduced by reducing the drying temperature. The drying temperature here does not refer to the temperature at which the resin composition is cured, but refers to the temperature at which the volatile components of the resin composition are removed, and may include the B stage at which a part of the resin composition is cured. Here, the "drying temperature" refers to a temperature that is higher than the boiling point of the volatile components and does not generate voids.

[0030] Storage modulus G' is 1.0×10 7The polyimide resin (A) having a temperature at which its molecular weight Pa falls within the range of −30 to 90° C. can be adjusted by the type of monomer that constitutes the repeating structural unit and Mw. Specifically, the storage modulus G' tends to decrease by combining a flexible monomer such as a dimer structure as a monomer with a structure having an aliphatic (including alicyclic) skeleton, while the storage modulus G' tends to increase by combining a structure in which an imide structure is directly bonded to a highly planar aromatic skeleton. In addition, the storage modulus G' tends to decrease by decreasing Mw. The storage modulus G' at 90° C. of a rigid polyimide resin, for example, a polyimide resin made of pyromellitic anhydride and diaminobiphenyl, is approximately 1.0×10 9 The storage modulus G' at 90°C of a flexible polyimide resin, for example, a polyimide resin made of dimer diamine and 1,2,4,5-cyclohexanetetracarboxylic dianhydride, is approximately 1.0 × 10 5 It is.

[0031] The Mw of the polyimide resin (A) is 10,000 to 100,000. By having it be 10,000 or more, even if the content of the thermally conductive filler (C) in the cured product is increased, good adhesion to other members can be maintained, and a high-quality cured product can be provided. Also, by having it be 100,000 or less, long-term heat resistance can be improved. A more preferred range is 15,000 to 80,000, and an even more preferred range is 20,000 to 75,000.

[0032] The amount of polyimide resin (A) is not limited, but in order to improve the bending strength of the cured product and to improve the suitability for substrate processing (particularly heat cycle resistance), it is preferably contained in an amount of 1 to 40% by mass relative to 100% by mass of the non-volatile components (solid content) of the composition, more preferably 7 to 27% by mass, and even more preferably 9 to 19% by mass.

[0033] The polyimide resin (A) is a polyimide resin having the general formula (1): [ka] (X 1is a tetravalent organic group for each repeating unit, 2 is a divalent organic group for each repeating unit, 1 and the imide bond are bonded to each other to form two imide rings. 1 Specific examples of X include tetracarboxylic acid residues, 2 Specific examples of the substituent include a diamine residue and a diisocyanate residue.

[0034] In this specification, the term "tetracarboxylic acid residue" refers to a group derived from a tetracarboxylic acid, or a tetracarboxylic acid derivative such as a tetracarboxylic acid dianhydride or a tetracarboxylic acid diester (hereinafter, these are referred to as "tetracarboxylic acids"). Furthermore, the term "diamine residue" refers to a group derived from a diamine (diamine compound), and the term "diisocyanate residue" refers to a residue derived from a diisocyanate (diisocyanate compound).

[0035] An "imido bond" is defined as a bond consisting of one nitrogen atom and two carbonyl bonds (C=O). 1 are bonded to each other to form an imide ring. An "imide ring" is a ring having an imide bond, and the number of elements forming one ring is 4 or more and 7 or less, preferably 5 or 6. The imide ring may be condensed with another ring. In addition, an "acid anhydride group" refers to a group represented by -C(=O)-OC(=O)-, and an "acid anhydride ring" refers to a ring formed by bonding an acid anhydride group to a carbon element.

[0036] The polyimide resin (A) may or may not have a reactive functional group with respect to the curable compound (B). Examples of the reactive functional group include the amino group, acid anhydride group, carboxy group, and maleimide group described above, as well as a phenolic hydroxyl group. When a polyimide resin (A) without a reactive functional group is used, a crosslinked structure with the curable compound (B) is not formed, but it is considered that the fluidity before curing and the stress relaxation effect after curing can be enhanced by blending a polyimide resin (A) having high flexibility and a specific range of Mw in the blending components of a resin composition that has a relatively high glass transition temperature when cured. In addition, it is considered that the polyimide resin (A) having a phenolic hydroxyl group can enhance the interaction between an aromatic ring having a phenolic hydroxyl group and an imide ring, and can combine a flexible structure derived from a dimer to enhance the fluidity before curing and to bring out a stress relaxation effect after curing.

[0037] The phenolic hydroxyl group refers to a hydroxyl group directly bonded to an aromatic ring. Suitable examples of the aromatic ring include a benzene ring, a naphthalene ring, and a pyridine ring. The phenolic hydroxyl group may be introduced into either the molecular chain end, a side group, or a side chain, or may be combined in any manner. The molecular chain end refers to a repeating structural unit that constitutes the molecular chain of the polyimide resin (A) at the end, or a non-repeating structure that is connected to the end.

[0038] The phenolic hydroxyl value of the polyimide resin (A) is preferably 1 to 50 mgKOH / g. By setting it in this range, the crosslink density can be made appropriate, and the substrate processing suitability, particularly the plating solution resistance (alkali resistance and acid resistance), can be more effectively improved. In addition, by setting the phenolic hydroxyl value in the above range, the crosslink density can be made appropriate, and the stress relaxation effect can be brought out. The phenolic hydroxyl value is more preferably 3 to 40 mgKOH / g, and further preferably 10 to 30 mgKOH / g. The phenolic hydroxyl value can be adjusted by the amount of monomer having a phenolic hydroxyl group, the introduction rate of the phenolic hydroxyl group to the molecular chain terminal, and / or the introduction rate of the phenolic hydroxyl group to the side chain.

[0039] To introduce a phenolic hydroxyl group into the molecular chain terminal of the polyimide resin (A), for example, an acid anhydride-terminated polyimide resin is synthesized, and then further reacted with an amine compound having a phenolic hydroxyl group represented by general formula (3). The acid anhydride-terminated polyimide resin may be replaced with a carboxylic acid-terminated polyimide resin, and the phenolic hydroxyl group may be introduced in a similar manner. [ka] In the general formula (3), Ar is an aromatic group which may have a substituent. Examples of the substituent include an alkyl group having 1 to 10 carbon atoms, a fluoroalkyl group, and a halogen atom. The same applies to Ar and the substituent in the general formulae (4) and (5) described later.

[0040] Another example is a method in which an amino-terminated polyimide resin is synthesized and then further reacted with an acid anhydride compound having a phenolic hydroxyl group represented by general formula (4) or a carboxylic acid compound having a phenolic hydroxyl group represented by general formula (5) to introduce a phenolic hydroxyl group at the end.

[0041] [ka] [ka]

[0042] Specific examples of the general formula (3) include 3-aminophenol, 4-aminophenol, 4-amino-o-cresol, 5-amino-o-cresol, 4-amino-2,3-xylenol, 4-amino-2,5-xylenol, 4-amino-2,6-xylenol, 4-amino-1-naphthol, 5-amino-2-naphthol, 6-amino-1-naphthol, and 4-amino-2,6-diphenylphenol. Specific examples of the general formula (4) include 3-hydroxyphthalic anhydride and 4-hydroxyphthalic anhydride. Specific examples of the general formula (5) include salicylic acid and oxybenzoic acid. Although examples of the general formulas (3) and (4) are given with one hydroxyl group, compounds having two or more hydroxyl groups bonded to Ar may also be used.

[0043] From the viewpoint of effectively improving the substrate processability, particularly the heat cycle resistance, of the cured product, a polyimide resin (A) having a phenolic hydroxyl group that satisfies at least one of the following (i) and (ii) is preferred. (i) It has a phenolic hydroxyl group at the molecular chain terminal, and a nitrogen atom forming an imide ring derived from a monoamine is bonded to the meta or ortho position of the aromatic ring having the phenolic hydroxyl group. (ii) It has a phenolic hydroxyl group at the molecular chain terminal, an aliphatic group directly bonded to the aromatic ring having the phenolic hydroxyl group, and a nitrogen atom forming an imide ring derived from a monoamine is bonded to the aliphatic group. As a result of intensive research, the inventors of the present invention found that the structure around the phenolic hydroxyl group at the molecular chain end is the structure around the crosslinking point, and therefore has a large effect on stress relaxation. It is believed that the structure (i) in which the hydroxyl group and the amino group are at the ortho or meta position reduces the interaction between the imide ring and another imide ring, improving stress relaxation properties. It is also believed that the structure (ii) in which the amino group is bonded via an aliphatic group rather than directly to the aromatic ring reduces the interaction between the imide ring and another imide ring, improving stress relaxation properties.

[0044] In order to obtain molecular chain ends that satisfy the above (i) and (ii), examples of monoamine compounds having a phenolic hydroxyl group used to end-capping an acid anhydride-terminated polyimide resin or a carboxy-terminated polyimide resin include the following compounds: m-aminophenol, o-aminophenol, 2-amino-5-ethylphenol, 2-(1-aminoethyl)phenol, 3-(2-aminoethyl)phenol, 4-(2-aminoethyl)phenol, 2-(2-aminoethyl)phenol, 2-(2-aminomethyl)phenol, 3-(2-aminomethyl)phenol, 2-(2-aminomethyl)phenol, 3-(2-aminomethyl)phenol, 4-(2-aminopropyl)phenol, etc.

[0045] The functional groups at the molecular chain ends of the polyimide resin (A) can be substantially all phenolic hydroxyl groups. In addition to the phenolic hydroxyl group ends, the polyimide resin (A) may also have molecular chain ends that have no functional groups. In addition to the phenolic hydroxyl group ends, the polyimide resin (A) may also have molecular chain ends that have other functional groups (such as acid anhydride groups).

[0046] The polyimide resin (A) having a molecular chain terminal without functional groups and a phenolic hydroxyl group terminal can be obtained, for example, by mixing an amine compound of general formula (3) and a monoamine compound for terminal blocking with an acid anhydride-terminated polyimide in a specific ratio and performing a terminal blocking reaction. Alternatively, the polyimide can be obtained by mixing a compound of general formula (4) and / or (5) with an acid anhydride compound and / or a carboxylic acid compound for terminal blocking with an amine-terminated polyimide in a specific ratio and performing a terminal blocking reaction. According to these methods, the amount of phenolic hydroxyl groups at the molecular chain terminals of the polyimide resin (A) can be easily adjusted.

[0047] Examples of monoamine compounds for blocking the ends include aliphatic amines such as methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, decylamine, stearylamine, dimethylamine, diethylamine, dipropylamine, and dibutylamine; alicyclic amines such as cyclohexylamine and dicyclohexylamine; aromatic amines such as aniline, toluidine, diphenylamine, and naphthylamine, and any mixtures thereof.

[0048] Examples of acid anhydrides for blocking the terminals include phthalic anhydride, 2,2'-biphenyldicarboxylic anhydride, 1,2-naphthalenedicarboxylic anhydride, 2,3-naphthalenedicarboxylic anhydride, 1,8-naphthalenedicarboxylic anhydride, 1,2-anthracenedicarboxylic anhydride, 2,3-anthracenedicarboxylic anhydride, L9-anthracenedicarboxylic anhydride, etc. Examples of carboxylic acids not having a phenolic hydroxyl group include carboxylic acids having a structure in which the phenolic hydroxyl group has been removed from the above-mentioned carboxylic acids having a phenolic hydroxyl group.

[0049] The polyimide resin (A) having a phenolic hydroxyl group terminal and other functional group terminal can be obtained, for example, by mixing an amine compound of general formula (3) and a monoamine compound having other functional groups in a specific ratio with an acid anhydride-terminated polyimide and performing an end-capping reaction. Similarly, the amine-terminated polyimide can be obtained by mixing a compound of general formula (4) and / or (5) with an acid anhydride compound and / or a carboxylic acid compound having other functional groups in a specific ratio and performing an end-capping reaction. According to this method, the amount of phenolic hydroxyl groups and other functional groups at the molecular chain terminal of the polyimide resin (A) can be adjusted. The other functional groups are not particularly limited. For example, nitro groups and cyano groups can be exemplified.

[0050] When the other functional group is an acid anhydride group, an acid anhydride-terminated polyimide may be synthesized, and then reacted with an amine compound having a phenolic hydroxyl group at a portion of the terminal to convert a portion of the acid anhydride terminal to a phenolic hydroxyl group. Similarly, when the other functional group is an amino group, an amino-terminated polyimide may be synthesized, and then reacted with a compound having one acid anhydride group having a phenolic hydroxyl group at a portion of the terminal.

[0051] In the above, an example was given in which a polyimide resin is synthesized and then reacted with a compound to be introduced into the molecular chain end, but the polyimide resin (A) may also be synthesized by mixing the compound to be introduced into the molecular chain end with the monomer for synthesizing the polyimide resin and polymerizing the mixture. This method can simplify the synthesis process.

[0052] From the viewpoint of improving plating solution resistance (alkali resistance, acid resistance), the ratio of the phenolic hydroxyl value to the total functional value (total) is preferably 50 to 100%, more preferably 70 to 100%. By introducing a phenolic hydroxyl group into the polyimide resin (A), the interaction between the aromatic ring having the phenolic hydroxyl group and the imide ring can be enhanced, and the internal stress relaxation of the polyimide resin (A) having a flexible structure derived from a dimer can be more effectively exhibited. When the polyimide resin does not contain a phenolic hydroxyl group, from the viewpoint of improving plating solution resistance (alkali resistance, acid resistance), it is preferable that the total average functional group amount of the amino group, the acid anhydride group, and the maleimide group is small, and it is more preferable that the total average functional group amount of the carboxy group, the amino group, the acid anhydride group, and the maleimide group is small. Specifically, it is preferable that the total average functional group amount of the amino group, the acid anhydride group, and the maleimide group is 0.5 or less, including 0, and more preferably 0.3 or less, including 0. In the case of a polyimide resin (A) containing a carboxy group, the average total amount of functional groups, carboxy groups, amino groups, acid anhydride groups and maleimide groups, is more preferably 0.5 or less, inclusive, and even more preferably 0.3 or less, inclusive.

[0053] To introduce a phenolic hydroxyl group into the side chain and / or side group of the polyimide resin (A), a method using an organic compound such as a diamine or diisocyanate having a phenolic hydroxyl group and / or a tetracarboxylic acid having a phenolic hydroxyl group is suitable. Alternatively, after synthesis of the polyimide resin, a compound having a phenolic hydroxyl group may be introduced into the side chain.

[0054] Suitable examples of diamines having a phenolic hydroxyl group include aromatic diamines such as bis(3-amino-4-hydroxyphenyl)hexafluoropropane, bis(3-amino-4-hydroxyphenyl)sulfone, bis(3-amino-4-hydroxyphenyl)propane, bis(3-amino-4-hydroxyphenyl)methylene, bis(3-amino-4-hydroxyphenyl)ether, bis(3-amino-4-hydroxy)biphenyl, 2,2'-ditrifluoromethyl-5,5'-dihydroxyl-4,4'-diaminobiphenyl, bis(3-amino-4-hydroxyphenyl)fluorene, and 2,2'-bis(trifluoromethyl)-5,5'-dihydroxybenzidine. Substituents may also be introduced at any position of these compounds.

[0055] Furthermore, a diamine represented by the following general formula (6) may be used. [ka]

[0056] R in the formula 1 represents a direct bond or a group containing carbon, hydrogen, oxygen, nitrogen, sulfur, or halogen. Examples of the group include a divalent hydrocarbon group having 1 to 30 carbon atoms, a divalent hydrocarbon group having 1 to 30 carbon atoms in which some or all of the hydrogen atoms have been substituted with halogen atoms, -(C=O)-, -SO2-, -O-, -S-, -NH-(C=O)-, -(C=O)-O-, a group represented by the following general formula (7), and a group represented by the following general formula (8). In the formula, r and s each independently represent an integer of 1 to 20, and R 2 represents a hydrogen atom or a methyl group.

[0057] [ka]

[0058] [ka]

[0059] Examples of the diamine represented by the general formula (6) include 2,2-bis(3-amino-4-hydroxyphenyl)propane, 9,9-bis(3-amino-4-hydroxyphenyl)fluorene, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, and 4,4'-diamino-3,3'-dihydroxybisphenyl.

[0060] Suitable examples of tetracarboxylic acids having a phenolic hydroxyl group include aromatic tetracarboxylic acids described below, which have a hydroxyl group on the substituent of the aromatic group.

[0061] Among these, from the viewpoint of more effectively improving plating solution resistance, diamines containing a phenolic hydroxyl group that satisfy at least one of the following (iii) and (iv) are preferred. (iii) X in general formula (1) 2 A part of the diamine residue X contains a phenolic hydroxyl group. 2 f, and a nitrogen atom derived from the diamine forming the imide ring is bonded to the aromatic ring having the phenolic hydroxyl group. (iv) X in general formula (1) 2 A part of the diamine residue X having a phenolic hydroxyl group 2 f, which has an aliphatic group directly bonded to the aromatic ring having the phenolic hydroxyl group, and a nitrogen atom derived from the diamine which forms the imide ring is bonded to the aliphatic group. By having a phenolic hydroxyl group that satisfies at least one of the above (iii) and (iv), the plating solution resistance of the cured product of the composition can be more effectively improved. By making the crosslinking point with the curable compound (B) a side group of the polyimide resin (A), a crosslinked structure can be effectively formed.

[0062] Suitable examples of diamines that satisfy the above (iii) or (iv) include the following general formulas (9) and (10): In formula (9), n is an integer of 1-10. [ka]

[0063] [ka]

[0064] X in general formula (1) 1 As described above, X is a tetravalent tetracarboxylic acid residue, each of which may have an independent structure for each repeating unit. 1 The tetracarboxylic acids used in the polymerization to obtain the above are not particularly limited. As the tetracarboxylic acids, aromatic tetracarboxylic acids containing an aromatic group, aliphatic tetracarboxylic acids containing an aliphatic group, and tetracarboxylic acids containing an aromatic group and an aliphatic group are preferably used. The aliphatic group refers to a hydrocarbon group, and may be linear, branched, cyclic (alicyclic structure), or a combination thereof. The aliphatic group may contain an unsaturated bond. The aliphatic group may also contain a heteroatom such as nitrogen, oxygen, sulfur, selenium, fluorine, chlorine, or bromine. The tetracarboxylic acids may be used alone or in combination of two or more kinds. The above-mentioned examples of monomers may also have a substituent as appropriate. Examples of the substituent include an alkyl group, a halogen atom, a nitro group, and a cyano group.

[0065] Examples of aromatic tetracarboxylic acids include pyromellitic dianhydride, 1,2,3,4-benzenetetracarboxylic dianhydride, 2,3',3,4'-biphenyltetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, and diphthalic anhydride represented by the following general formula (11). [ka] X in the formula 5 represents an organic group which may have a divalent substituent (e.g., a hydrocarbon group having 1 to 10 carbon atoms), -O-, -CO-, -SO2-, -S-, -SO2-, -CONH-, -COO-, or a linking group such as -OCO-, -C(CF3)2-, -COO-Z-OCO-, or -O-Ph-C(CH3)2-Ph-O-. The Z is, for example, -C6H4-, -(CH2) n Examples of the substituent include -, -CH2-CH(-OC(=O)-CH3)-CH2-. These may contain a substituent. Examples of the substituent include an alkyl group, a halogen, and a carbonyl group. The same applies to the tetracarboxylic acid described below. Specific examples include 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfone tetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, p-phenylene bis(trimellitic acid monoester acid anhydride), and ethylene glycol bisanhydrotrimellitate.

[0066] X in general formula (1) of polyimide resin (A) 1 The structure of is not limited, but it is preferable to use an aliphatic group-containing X having a dimer structure that adjusts the storage modulus and synergistically brings out a stress relaxation effect with the dimer structure to improve the suitability for substrate processing. Specifically, the structure of is preferably a dimer structure that has an aliphatic group-containing X having a dimer structure that has a stress relaxation effect with the dimer structure to improve the bending strength and heat cycle resistance. 1 It is preferable that X contains a. 1It is sufficient that a has an aliphatic group, and it may also contain an aromatic group.

[0067] Tetracarboxylic acids having an aliphatic group include a chain hydrocarbon structure and / or an alicyclic hydrocarbon structure which may contain an aromatic group. The "chain hydrocarbon structure" is a straight chain hydrocarbon structure and / or a branched hydrocarbon structure which may contain an unsaturated bond. The "alicyclic hydrocarbon structure" is an alicyclic hydrocarbon which may contain an unsaturated bond, and may be monocyclic or polycyclic. These may contain a substituent.

[0068] Specific examples of tetracarboxylic acids having an aliphatic group include tetracarboxylic dianhydrides having a chain hydrocarbon structure, such as 1,2,3,4-butanetetracarboxylic acid, 1,2,3,4-pentanetetracarboxylic acid, 1,2,4,5-pentanetetracarboxylic acid, 1,2,3,4-hexanetetracarboxylic acid, and 1,2,5,6-hexanetetracarboxylic acid. Also, cyclobutane-1,2,3,4-tetracarboxylic acid, cyclopentane-1,2,3,4-tetracarboxylic acid, cyclohexane-1,2,3,4-tetracarboxylic acid, cyclohexane-1,2,4,5-tetracarboxylic acid, 1-carboxymethyl-2,3,5-cyclopentanetricarboxylic acid, 3-carboxymethyl-1,2,4-cyclopentanetricarboxylic acid, rel-dicyclohexyl-3,3',4,4'-tetracarboxylic acid, tricyclo[4.2.2.02,5]deca -9-ene-3,4,7,8-tetracarboxylic acid, 5-carboxymethylbicyclo[2.2.1]heptane-2,3,6-tricarboxylic acid, bicyclo[2.2.1]heptane-2,3,5,6-tetracarboxylic acid, bicyclo[2.2.2]octane-7-ene-2,3,6,7-tetracarboxylic acid, bicyclo[3.3.0]octane-2,4,6,7-tetracarboxylic acid, 7,8-diphenylbicyclo[2.2.2]octane-7-ene-2,3,5,6-tetracarboxylic acid, 4,8-diphenylbicyclo[2.2.2]octane-7-ene-2,3,5,6-tetracarboxylic acid, Cyclo-, bicyclo-, and tricyclotetracarboxylic acids such as phenyl-1,5-diazabicyclooctane-2,3,6,7-tetracarboxylic acid, 9-oxatricyclo[4.2.1.02,5]nonane-3,4,7,8-tetracarboxylic acid, and 9,14-dioxopentacyclo[8.2.11,11.14,7.02,10.03,8]tetradecane-5,6,12,13-tetracarboxylic acid; spiro-ring-containing tetracarboxylic acids such as 2,8-dioxaspiro[4.5]decane-1,3,7,9-tetradecane; Examples of the tetracarboxylic acid dianhydride include tetracarboxylic acid dianhydrides having an alicyclic hydrocarbon structure, such as 5-(2,5-dioxotetrahydrofuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic acid anhydride, 1,3,3a,4,5,9b-hexahydro-5(tetrahydro-2,5-dioxo-3-furanyl)naphtho[1,2-c]furan-1,3-dione, and 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic acid anhydride.

[0069] X having an aliphatic group 1 Among the structures a, from the viewpoint of more effectively exerting stress relaxation, it is preferable to have a structure S that satisfies at least one of the following (I) and (II). (I) The X constituting the imide ring 1 At least one of the carbon atoms in the X constituting the other imide ring 1 At least one of the carbons in the (II) the X constituting each of the two imide rings 1 At least one of the carbons in each independently has a structure directly bonded to an aliphatic structure, or contains an aliphatic structure that is one of the constituent elements. Specific examples of compounds that satisfy the above condition (I) include the chemical formulas (Ia) to (Id). Note that the chemical formulas (Ib) to (Id) also satisfy the above condition (II). In the formulas, * indicates the bonding site with the imide group. [ka]

[0070] Specific examples that satisfy the above (II) include the chemical formulas (II-a) to (II-v).

[0071] [ka]

[0072] X forms an imide ring 1 X has structure S, in which the carbon in the X is directly connected to a chain hydrocarbon structure that is an aliphatic structure. 1 Examples of a include compounds represented by chemical formulas (II-a) and (II-v). X forming an imide ring 1 X has a structure S that contains an alicyclic hydrocarbon structure among aliphatic structures in which carbon is one of the constituent elements. 1 An example of a is a compound represented by the chemical formula (II-b). 1 The carbon atom of X is directly bonded to the alicyclic hydrocarbon structure of the aliphatic structure and forms the other imide ring. 1 X has a structure S that contains an alicyclic hydrocarbon structure among aliphatic structures in which carbon is one of the constituent elements. 1An example of a is represented by the chemical formula (II-c). Note that it is sufficient that each of the two imide rings independently satisfies at least one of the above (I) and (II), and an aromatic ring may be included as represented by the chemical formula (II-d).

[0073] X having an aliphatic group 1 The ratio of a to X constituting the polyimide resin (A) is 1 With respect to 100 mol %, the range is preferably 60 to 100 mol %, more preferably 75 to 100 mol %, and even more preferably 85 to 100 mol %. 1 By using 60 to 100 mol % of a, the heat cycle resistance (suitability for substrate processing) becomes more excellent. 1 The proportion of a is the ratio of X to X among the raw material monomers used in synthesizing polyimide resin (A). 1 The ratio of X having an aliphatic group to the total monomers that are the residues (100 mol %) 1 It can be calculated from the content (mol%) of the monomer that is the residue of a. Usually, the content of X having an aliphatic group in 100 mol% of the monomer that is a tetracarboxylic acid used in the polymerization of the polyimide resin (A) is 1 By adjusting the charge rate of the monomer containing a to 60 to 100 mol %, it is possible to achieve the ratio of the constituent components derived from the monomer of the polyimide resin (A).

[0074] X in general formula (1) 2 As described above, X is a divalent organic group which may have an independent structure for each repeating unit. 2 As mentioned above, suitable examples of the organic compound used in the polymerization to obtain X include diamines and diisocyanates. 2 At least a portion of the residues X are derived from dimer diamine and / or dimer diisocyanate. 2 d.

[0075] X with dimeric structure 2 The proportion of d is the ratio of X that constitutes the polyimide resin (A). 2When the total is taken as 100 mol %, 60 to 100 mol % is preferred. By setting it in this range, packing of the polyimide resin (A) can be appropriately inhibited, dispersibility with the curable compound (B) and the thermally conductive filler (C) can be effectively increased, and both substrate processability and bending strength can be achieved in a well-balanced manner. A more preferred range is 75 to 100 mol %, and an even more preferred range is 85 to 100 mol %. X having a dimer structure 2 The ratio of d is the ratio of X to X among the raw material monomers used in synthesizing polyimide resin (A). 2 The proportion of X having a dimer structure in 100 mol% of all monomers that are residues 2 It can be determined from the content (mol %) of the monomer in which d is the residue.

[0076] X in the general formula (1) of the polyimide resin (A) 2 In the above, the residue X having the dimer structure 2 X other than the monomer that forms d 2 The other diamines to be the monomers are not particularly limited. Specific examples include diamine compounds having an aliphatic group (a chain hydrocarbon structure and / or an alicyclic hydrocarbon structure that may contain an unsaturated bond) that may have a substituent, an aromatic ring, and any combination thereof.

[0077] Specific examples of diamines other than those having a dimer structure include 1,4-diaminobenzene, 1,3-diaminobenzene, 1,2-diaminobenzene, 1,5-diaminonaphthalene, 1,8-diaminonaphthalene, 2,3-diaminonaphthalene, 2,6-diaminotoluene, 2,4-diaminotoluene, 3,4-diaminotoluene, 4,4'-diaminodiphenylmethane, 3,4'-diaminodiphenylether, 4,4'-diaminodiphenylether, 4,4'-diamino-1,2-diphenylethane, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminobenzophenone, 4,4'- Examples of the diamine include aromatic diamines such as diaminodiphenylsulfone, 3,3'-diaminobenzophenone, and 3,3'-diaminodiphenylsulfone; aliphatic diamines such as ethylenediamine, 1,3-propanediamine, 1,4-butanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,9-nonanediamine, 1,12-dodecamethylenediamine, and metaxylenediamine; and alicyclic diamines such as isophoronediamine, norbornanediamine, 1,2-cyclohexanediamine, 1,3-cyclohexanediamine, 1,4-cyclohexanediamine, 4,4'-diaminodicyclohexylmethane, and piperazine.

[0078] In addition, diamines having a phenolic hydroxyl group such as bis(3-amino-4-hydroxyphenyl)hexafluoropropane, bis(3-amino-4-hydroxyphenyl)sulfone, bis(3-amino-4-hydroxyphenyl)propane, bis(3-amino-4-hydroxyphenyl)methylene, bis(3-amino-4-hydroxyphenyl)ether, bis(3-amino-4-hydroxy)biphenyl, 2,2'-ditrifluoromethyl-5,5'-dihydroxyl-4,4'-diaminobiphenyl, bis(3-amino-4-hydroxyphenyl)fluorene, and 2,2'-bis(trifluoromethyl)-5,5'-dihydroxybenzidine may be mentioned. Any substituent may be introduced at any position of the above diamine.

[0079] The polyimide resin (A) may contain, within the scope of the present disclosure, X1 residue, X 2 Residues derived from monomers other than the amino groups may be included. For example, a polyamine compound having three or more amino groups may be used. Examples of polyamine compounds having three or more amino groups include 1,2,4-triaminobenzene and 3,4,4'-triaminodiphenyl ether.

[0080] The polyimide resin (A) can be produced by various known methods. Specific examples include a method of converting a polyimide precursor, a polyamic acid resin or a polyamic acid ester resin, into an imide group by heating to cyclize it. For example, a method of synthesizing a polyamic acid resin includes a method of reacting a tetracarboxylic dianhydride with a diamine. More specifically, a polyamic acid resin, which is a polyimide precursor, can be produced by dissolving a monomer containing a tetracarboxylic dianhydride and a diamine in a solvent and stirring the resulting mixture at a temperature of, for example, 60 to 120°C for 0.1 to 2 hours to polymerize the monomer.

[0081] In the polyimide resin (A), the method of adjusting the number of terminal functional groups by the reaction of a monofunctional compound is suitable as a method of making the total average number of functional groups selected from amino groups, acid anhydride groups, and maleimide groups 1 or less, including 0. The amino group and acid anhydride group can be introduced from a monomer. The maleimide group can be introduced into the molecular chain end or side chain by a method of introducing a maleimide group-containing compound, or by reacting a terminal amine compound with maleic anhydride. When introducing a maleimide group or a phenolic hydroxyl group, it may be introduced at the stage of synthesizing the polyamic acid resin, or after the polyimide resin is obtained. The same applies when passing through a polyamic acid ester resin described later. The amino group, acid anhydride group, and maleimide group may be introduced into the side chain or side group. The phenolic hydroxyl group may also be introduced into the side chain or side group. When introducing these functional groups into the side chains or side groups, there are a method of using a compound having these functional groups in a monomer for polymerizing the polyimide resin (A), and a method of introducing a phenolic hydroxyl group into the side chain or side group after synthesizing a polyimide resin precursor or a polyimide resin.

[0082] Examples of the synthesis method of the polyamic acid ester resin include a method of obtaining a diester from a tetracarboxylic dianhydride and an alcohol, and then reacting it with a diamine in the presence of a condensing agent, and a method of obtaining a diester from a tetracarboxylic dianhydride and an alcohol, and then converting the remaining dicarboxylic acid into an acid chloride and reacting it with a diamine. Also suitable is a method of reacting a tetracarboxylic dianhydride with a diisocyanate to obtain a polyimide precursor, and then obtaining a polyimide resin.

[0083] Examples of organic solvents used in polymerization include N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, dioxane, tetrahydrofuran, diglyme, triglyme, and cresol. The solvents are used alone or in combination of two or more. Aromatic hydrocarbons such as xylene and toluene can also be used in combination.

[0084] The method for obtaining a polyimide resin by imidizing a polyimide precursor is not particularly limited, but may be, for example, a method of heating in a solvent at a temperature of 80 to 400° C. for 0.5 to 50 hours. At this time, a catalyst and / or a dehydrating agent may be used as necessary.

[0085] Examples of the reaction catalyst include aliphatic tertiary amines such as triethylamine, aromatic tertiary amines such as dimethylaniline, and heterocyclic tertiary amines such as pyridine, picoline, isoquinoline, etc. Examples of the dehydrating agent include aliphatic acid anhydrides such as acetic anhydride, and aromatic acid anhydrides such as benzoic anhydride.

[0086] The imidization rate (imide ring formation rate) is not limited, but from the viewpoint of effectively exerting the effects of alkali resistance and acid resistance (plating solution resistance), it is preferably 80% or more, more preferably 90% or more, and even more preferably 95 to 100%. The imidization rate can be determined by NMR or IR analysis, etc.

[0087] 1-2. Curing compound (B) The curable compound (B) is one or more selected from the group consisting of epoxy compounds (b1), cyanate ester compounds (b2), maleimide compounds (b3), polyphenylene ether compounds (b4) and nadimide compounds (b5). The epoxy compound (b1) may be used in combination with an active ester compound. The curable compound (B) may be used alone or in combination with two or more types of resins, regardless of whether they are the same or different resins. In addition, a curing agent and a curing accelerator other than the above may be used in combination.

[0088] In the present composition, the curable compound (B) is preferably used in an amount of 10 to 98% by mass, more preferably -30 to 90% by mass, and even more preferably 45 to 85% by mass, based on 100% by mass of the components excluding the thermally conductive filler (C) and the solvent. The average number of functional groups in the curable compound (B) is calculated for each of the curable compounds (B) having the same skeleton.

[0089] From the viewpoint of more effectively improving long-term heat resistance, among (b1) to (b5), a combination of the cyanate ester compound (b2) and the maleimide compound (b3), and a combination of the maleimide compound (b3) and the polyphenylene ether compound (b4) are preferred. From the viewpoint of more effectively improving bending strength, a combination of the maleimide compound (b3) and the nadiimide compound (b5) is preferred.

[0090] The epoxy compound (b1) refers to a curable resin having an epoxy group. The epoxy compound (b1) is preferably used in combination with an active ester compound. The active ester compound refers to a compound that has one or more ester groups in one molecule that react with an epoxy group and cures an epoxy resin. Examples of commercially available active ester compounds include "HPC-8000-65T", "EXB9416-70BK" and "EXB8100-65T" manufactured by DIC Corporation.

[0091] By using an active ester compound, an ester group is generated by the reaction between the epoxy compound (b1) and the active ester compound. Therefore, the polarity can be lowered compared to the case where a phenol-based curing agent is used. As a result, the compatibility between the dimer structure of the polyimide resin (A) and the epoxy compound (b1) can be effectively increased.

[0092] Specific examples of the epoxy compound (b1) include glycidyl ether type epoxy resins; glycidyl amine type epoxy resins such as tetraglycidyl diaminodiphenylmethane, triglycidyl para-aminophenol, triglycidyl meta-aminophenol, tetraglycidyl meta-xylylenediamine, and sorbitol polyglycidyl ether; glycidyl ester type epoxy resins such as diglycidyl phthalate, diglycidyl hexahydrophthalate, and diglycidyl tetrahydrophthalate; cyclic aliphatic (alicyclic) epoxy resins such as epoxycyclohexylmethyl-epoxycyclohexanecarboxylate and bis(epoxycyclohexyl)adipate; bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, and bisphenol AD ​​type epoxy resins. Other examples include cresol novolac type epoxy resins, phenol novolac type epoxy resins, α-naphthol novolac type epoxy resins, bisphenol A type novolac type epoxy resins, dicyclopentadiene type epoxy resins, tetrabromobisphenol A type epoxy resins, and brominated phenol novolac type epoxy resins.

[0093] The cyanate ester compound (b2) refers to a curable resin having a cyanate group. Examples of the cyanate ester compound (b2) include bisphenol A type cyanate ester resin, bisphenol F type cyanate ester resin, bisphenol E type cyanate ester resin, bisphenol S type cyanate ester resin, bisphenol sulfide type cyanate ester resin, phenylene ether type cyanate ester resin, naphthylene ether type cyanate ester resin, biphenyl type cyanate ester resin, tetramethylbiphenyl type cyanate ester resin, polyhydroxynaphthalene type cyanate ester resin, phenol novolac type cyanate ester resin, cresol novolac type cyanate ester resin, triphenyl Examples of the cyanate ester resin include methane type cyanate ester resin, tetraphenylethane type cyanate ester resin, dicyclopentadiene-phenol addition reaction type cyanate ester resin, phenol aralkyl type cyanate ester resin, naphthol novolac type cyanate ester resin, naphthol aralkyl type cyanate ester resin, naphthol-phenol co-condensed novolac type cyanate ester resin, naphthol-cresol co-condensed novolac type cyanate ester resin, aromatic hydrocarbon formaldehyde resin modified phenol resin type cyanate ester resin, biphenyl modified novolac type cyanate ester resin, and anthracene type cyanate ester resin.

[0094] Commercially available cyanate ester compounds (b2), such as phenol novolac type cyanate ester resins ("PT-30" and "PT-60" manufactured by Lonza Japan), and prepolymers obtained by trimerizing bisphenol type cyanate ester resins ("BA-230S", "BA-3000S", "BTP-1000S" and "BTP-6020S" manufactured by Lonza Japan), may also be used.

[0095] The maleimide compound (b3) refers to a curable resin having a maleimide group. The type of the maleimide compound (b3) is not particularly limited. From the viewpoint of long-term heat resistance, the average number of maleimide groups is preferably 1.5 to 4, and more preferably 2 or more.

[0096] The Mw of the maleimide compound (b3) is not particularly limited, but from the viewpoint of suppressing volatilization during drying, it is preferably 100 or more, and more preferably 150 or more. The upper limit of Mw is not particularly limited, but in consideration of availability, it is 8000 or less, more preferably 5000 or less.

[0097] The maleimide compound (b3) can be a polyfunctional maleimide obtained by reacting a polyfunctional amine with maleic anhydride. Examples of polyfunctional amines include isophorone diamine, dicyclohexylmethane-4,4'-diamine, and Huntsman Corporation's Jeffamine D-230, HK-511, D-400, XTJ-582, D-2000, XTJ-578, XTJ-509, XTJ-510, T-403, and T-5000, which have terminal aminated polypropylene glycol skeletons, and XTJ-500, XTJ-501, XTJ-502, XTJ-504, XTJ-511, XTJ-512, and XTJ-590, which have terminal aminated ethylene glycol skeletons, and XTJ-542, XTJ-533, XTJ-536, XTJ-548, and XTJ-559, which have terminal aminated polytetramethylene glycol skeletons.

[0098] Examples of the maleimide compound (b3) include 4,4'-diphenylmethane bismaleimide, m-phenylene bismaleimide, p-phenylene bismaleimide, 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane, bis-(3-ethyl-5-methyl-4-maleimidophenyl)methane, 4-methyl-1,3-phenylene bismaleimide, N,N'-ethylene dimaleimide, N,N'-hexamethylene dimaleimide, bis(4-maleimidophenyl)ether, bis(4-maleimidophenyl)sulfone, 3,3'-dimethyl-5,5'-diene Resins with two maleimide groups in the molecule, such as bisphenol A diphenyl ether bismaleimide, biphenyl aralkyl maleimide, polyphenylmethane maleimide (CAS NO: 67784-74-1, reaction product of a polymer of formaldehyde and aniline with maleic anhydride), N,N'-(toluene-2,6-diyl) bismaleimide, 4,4'-diphenyl ether bismaleimide, 4,4'-diphenylsulfone bismaleimide, 1,3-bis(3-maleimidophenoxy)benzene Zene, 1,3-bis(4-maleimidophenoxy)benzene, N,N'-ethylene bismaleimide, N,N'-trimethylene bismaleimide, N,N'-propylene bismaleimide, N,N'-tetramethylene bismaleimide, N,N'-pentamethylene bismaleimide, N,N'-(1,3-pentanediyl)bis(maleimide), N,N'-hexamethylene bismaleimide, N,N'-(1,7-heptanediyl)bismaleimide, N,N'-(1,8-octanediyl)bismaleimide, N,N'-(1,9-notanediyl)bismaleimide dodecane, N,N'-(1,10-decanediyl)bismaleimide, N,N'-(1,11-undecanediyl)bismaleimide, N,N'-(1,12-dodecanediyl)bismaleimide, N,N'-[(1,4-phenylene)bismethylene]bismaleimide, N,N'-[(1,2-phenylene)bismethylene]bismaleimide, N,N'-[(1,3-phenylene)bismethylene]bismaleimide, 1,6'-bismaleimido-(2,2,4-trimethyl)hexane, N,N'-[(methylimino)bis(4,1-phenylene)]bismaleimide, N,N'-(2-hydroxypropane-1,3-diylbisiminobiscarbonylbisethylene)bismaleimide, N,N'-(dithiobisethylene)bismaleimide, N,N'-[hexamethylenebis(iminocarbonylmethylene)]bismaleimide, N,N'-carbonylbis(1,4-phenylene)bismaleimide, N,N',N''-[nitrilotris(ethylene)]trismaleimide, N,N',N''-[nitrilotris(4,1-phenylene)]trismaleimide, N,N'-[p-phenylenebis(oxy-p-phenylene)]bismaleimide bismaleimide, N,N'-[methylenebis(oxy)bis(2-methyl-1,4-phenylene)]bismaleimide, N,N'-[methylenebis(oxy-p-phenylene)]bis(maleimide), N,N'-[dimethylsilylenebis[(4,1-phenylene)(1,3,4,-oxadiazole-5,2-diyl)(4,1-phenylene)]]bismaleimide, N,N'-[(1,3-phenylene)bisoxybis(3,1-phenylene)]bismaleimide, 1,1'-[3'-oxospiro[9H-xanthene-9,1'(3'H)-isobenzofuran]-3 ,6-diyl]bis(1H-pyrrole-2,5-dione), N,N'-(3,3'-dichlorobiphenyl-4,4'-diyl)bismaleimide, N,N'-(3,3'-dimethylbiphenyl-4,4'-diyl)bismaleimide, N,N'-(3,3'-dimethoxybiphenyl-4,4'-diyl)bismaleimide, N,N'-[methylenebis(2-ethyl-4,1-phenylene)]bismaleimide, N,N'-[methylenebis(2,6-diethyl-4,1-phenylene)]bismaleimide, N,N'-[methylenebis(2-bromo-6-ethyl-4,1 -phenylene)]bismaleimide, N,N'-[methylenebis(2-methyl-4,1-phenylene)]bismaleimide, N,N'-[ethylenebis(oxyethylene)]bismaleimide, N,N'-[sulfonylbis(4,1-phenylene)bis(oxy)bis(4,1-phenylene)]bismaleimide, N,N'-[naphthalene-2,7-diylbis(oxy)bis(4,1-phenylene)]bismaleimide, N,N'-[p-phenylenebis(oxy-p-phenylene)]bismaleimide, N,N'-[(1,3-phenylene)bisoxybis(3,1-phenylene)]bismaleimide, N,N'-(3,6,9-trioxaundecane-1,11-diyl)bismaleimide, N,N'-[isopropylidenebis[p-phenyleneoxycarbonyl(m-phenylene)]]bismaleimide, N,N'-[isopropylidenebis[p-phenyleneoxycarbonyl(p-phenylene)]]bismaleimide, N,N'-[isopropylidenebis[(2,6-dichlorobenzene-4,1-diyl)oxycarbonyl(p-phenylene)]]bismaleimide, N,N'-[(phenylimino)bis bis(4,1-phenylene)]bismaleimide, N,N'-[azobis(4,1-phenylene)]bismaleimide, N,N'-[1,3,4-oxadiazole-2,5-diylbis(4,1-phenylene)]bismaleimide, 2,6-bis[4-(maleimido-N-yl)phenoxy]benzonitrile, N,N'-[1,3,4-oxadiazole-2,5-diylbis(3,1-phenylene)]bismaleimide, N,N'-[bis[9-oxo-9H-9-phospha(V)-10-oxaphenanthren-9-yl]methylenebis (p-phenylene)] bismaleimide, N,N'-[hexafluoroisopropylidenebis[p-phenyleneoxycarbonyl(m-phenylene)]] bismaleimide, N,N'-[carbonylbis[(4,1-phenylene)thio(4,1-phenylene)]] bismaleimide, N,N'-carbonylbis(p-phenyleneoxyp-phenylene) bismaleimide, N,N'-[5-tert-butyl-1,3-phenylenebis[(1,3,4-oxadiazole-5,2-diyl)(4,1-phenylene)]] bismaleimide, N,N' -[Cyclohexylidenebis(4,1-phenylene)]bismaleimide, N,N'-[methylenebis(oxy)bis(2-methyl-1,4-phenylene)]bismaleimide, N,N'-[5-[2-[5-(dimethylamino)-1-naphthylsulfonylamino]ethylcarbamoyl]-1,3-phenylene]bismaleimide, N,N'-(oxybisethylene)bismaleimide, N,N'-[dithiobis(m-phenylene)]bismaleimide, N,N'-(3,6,9-trioxaundecane-1,11-diyl)bismaleimide, N,Examples of polyfunctional maleimides include N'-(ethylenebis-p-phenylene)bismaleimide, BMI-689, BMI-1500, BMI-1700, BMI-3000, BMI-5000, and BMI-9000 manufactured by Designer Molecules, and ODA-BMI and BAFBMI manufactured by JFE Chemical Corporation.

[0099] When the maleimide compound (b3) is crosslinked by radicals, a radical polymerization initiator can be added. Specific examples include azo compounds and organic peroxides. The polymerization initiators are used alone or in combination of two or more. Examples of azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl 2,2'-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane]. Examples of organic peroxides include benzoyl peroxide, t-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl)peroxydicarbonate, t-butyl peroxy 2-ethylhexanoate, t-butyl peroxy neodecanoate, t-butyl peroxypivalate, (3,5,5-trimethylhexanoyl)peroxide, dipropionyl peroxide, and diacetyl peroxide.

[0100] The polyphenylene ether compound (b4) has a repeating unit having a structure represented by the following general formula (14) and contains a curable functional group. [ka] R 11 , R12 , R 13 and R 14 is, independently for each repeating unit, a hydrogen atom, a halogen atom (a fluorine atom, a chlorine atom, a bromine atom, etc.), an alkyl group which may have a substituent (a linear or branched compound having 1 to 6 carbon atoms, such as a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a tert-butyl group, a pentyl group, a heptyl group, etc., and an alicyclic compound such as a cyclohexyl group), an alkoxy group which may have a substituent (an alkoxy group having 1 to 6 carbon atoms, such as a methoxy group, an ethoxy group, a butoxy group, a propoxy group, etc.), an aryl group which may have a substituent (a phenyl group, a naphthyl group, etc.), an amino group which may have a substituent, a carboxy group, a nitro group, a cyano group, etc.

[0101] From the viewpoint of long-term heat resistance, the polyphenylene ether compound (b4) preferably has an average number of curable functional groups of 1 to 10, more preferably 2 or more.

[0102] The Mw of the polyphenylene ether compound (b4) is not particularly limited, but from the viewpoint of bending strength, it is preferably 200 or more, and more preferably 500 or more. The upper limit of Mw is not particularly limited, but in consideration of availability, it is 10,000 or less.

[0103] Specific examples of the polyphenylene ether compound (b4) include poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2,6-dimethyl-1,4-phenylene ether), poly(2-methyl-6-phenyl-1,4-phenylene ether), poly(2,6-dichloro-1,4-phenylene ether), and copolymers of 2,6-dimethylphenol and other phenols (e.g., 2,3,6-trimethylphenol, 2-methyl-6-butylphenol, etc.). In addition, polyphenylene ether copolymers obtained by coupling 2,6-dimethylphenol with biphenols or bisphenols, and poly(2,6-dimethyl-1,4-phenylene ether) and the like, which are heated with phenolic compounds such as bisphenols or trisphenols in a solvent such as toluene in the presence of an organic peroxide, are included, which have a linear or branched structure and are obtained by redistribution reaction.

[0104] The nadiimide compound (b5) is not particularly limited as long as it has two or more nadiimide groups in the molecule. A suitable example of the nadiimide compound (b5) is a compound having a structure represented by the following general formula (15). [ka] R 21 R is an alkylene group having 1 to 20 carbon atoms which may have a substituent (for example, an alkylene group such as a methylene group, an ethylene group, a propylene group, a butylene group, a pentylene group, or a heptylene group), an alicyclic group such as a cyclohexylene group, a phenylene group, a biphenylene group, a naphthylene group, or any combination thereof. 22 and R 23 is a curable functional group such as an allyl group or a (meth)acrylate group.

[0105] Commercially available products include "BANI-M" and "BANI-X" manufactured by Maruzen Petrochemical Co., Ltd.

[0106] 1-3. Thermally conductive filler (C) The thermally conductive filler (C) is a compound that imparts thermal conductivity to the cured product of the composition. From the viewpoint of thermal conductivity, the thermal conductivity of the thermally conductive filler is preferably 0.5 W / (m·K) or more, more preferably 1.0 W / (m·K) or more, and even more preferably 1.5 W / (m·K) or more. As the thermally conductive filler (C), a thermally conductive inorganic filler or a thermally conductive organic-inorganic hybrid filler can be used. The content of the thermally conductive filler (C) may be appropriately adjusted depending on the application, and is usually 5 to 95 mass% relative to 100 mass% of the non-volatile components of the composition. The shape of the thermally conductive filler (C) is not particularly limited. For example, it may be spherical, powdery, fibrous, needle-like, or scaly. By using multiple types of thermally conductive fillers with different particle sizes and shapes, the thermally conductive filler (C) may be highly loaded. The thermally conductive filler (C) may be used alone or in combination of two or more types.

[0107] Specific examples of thermally conductive inorganic fillers include alumina, aluminum hydroxide, zirconium hydroxide, barium hydroxide, calcium hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, zinc carbonate, barium carbonate, magnesium sulfate, titanium oxide, tin oxide, aluminum oxide, magnesium oxide, zirconium oxide, calcium oxide, magnesium oxide, zinc oxide, molybdenum oxide, antimony oxide, nickel oxide, calcium silicate, beryllia, calcium titanate, silicon carbide, silicon nitride, aluminum nitride, boron nitride, titanium white, Examples of fillers include metal compounds such as palladium oxide, zinc borate, and aluminum borate; talc; clay; mica; metal oxides and metal nitrides such as glass fiber, kaolin, hydrotalcite, wollastonite, xonotlite, calcium hydrogen phosphate, calcium phosphate, glass flakes, hydrated glass, and sepiolite; hydrated metal compounds; silica-based fillers such as fused crushed silica, fused spherical silica, crystalline silica, non-crystalline silica, secondary agglomerated silica, fine silica, hollow silica, and porous silica; and nitride-based and carbon-based fillers such as silicon carbide, silicon nitride, titanium carbide, and diamond. Among these, alumina, aluminum oxide, aluminum nitride, and boron nitride are more preferable, and alumina and boron nitride are particularly preferable from the viewpoint of effectively enhancing long-term heat resistance.

[0108] Specific examples of the thermally conductive organic-inorganic hybrid filler include fillers in which the surface of the inorganic filler listed above is coated with a resin or a dispersant. A known method can be applied as a method for coating the surface of the thermally conductive inorganic filler with a resin or a dispersant. In this case, in order to effectively bring out the thermal conductive properties of the thermally conductive inorganic filler, it is preferable that the inorganic filler is exposed. The surface of the thermally conductive inorganic filler can be surface-treated with, for example, a silane-based, titanate-based, or aluminate-based coupling agent. The surface treatment can increase the dispersibility of the thermally conductive filler in the binder component. In addition, the interfacial adhesive strength between the binder component and the thermally conductive filler can also be increased.

[0109] Examples of silane coupling agents include aminosilanes such as γ-aminopropyltriethoxysilane, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, γ-aminopropyltrimethoxysilane, and γ-ureidopropyltriethoxysilane; epoxysilanes such as γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; mercaptosilanes such as 3-mercaptopropyltrimethoxysilane; and vinylsilanes such as p-styryltrimethoxysilane, vinyltrichlorosilane, vinyltris(β-methoxyethoxy)silane, vinyltrimethoxysilane, vinyltriethoxysilane, and γ-methacryloxypropyltrimethoxysilane.

[0110] Examples of titanate coupling agents include isopropyl triisostearoyl titanate, isopropyl tri(N-aminoethyl aminoethyl) titanate, tetra(2,2-diallyloxymethyl-1-butyl)bis(ditridecyl)phosphite titanate, bis(dioctyl pyrophosphate)oxyacetate titanate, bis(dioctyl pyrophosphate)ethylene titanate, diisopropyl bis(dioctyl phosphate) titanate, tetraisopropyl bis(dioctyl phosphite) titanate, and tetraoctyl bis(ditridecyl phosphite) titanate.

[0111] In addition, a preferred embodiment is one in which the surface of the thermally conductive inorganic filler is coated with a fluorine-based resin. From the viewpoint of maintaining good thermal conductivity, it is preferred that the thermally conductive inorganic filler is exposed at the portion where the thermally conductive inorganic filler contacts each other.

[0112] The method of adding the thermally conductive filler (C) is not particularly limited, and a conventionally known method can be used. Suitable examples include a method of adding the filler to a polymerization reaction liquid before or during polymerization of the polyimide resin (A), a method of kneading the filler into the polyimide resin (A) using a three-roll mill, and a method of preparing a dispersion containing the filler and mixing it with the polyimide resin (A). In addition, in order to disperse the filler well and stabilize the dispersion state, a dispersant, a thickener, etc. can be used within a range that does not affect the physical properties of the resin composition.

[0113] 1-4.Heat stabilizer (D) The composition may contain a heat stabilizer (D) as an optional component. The heat stabilizer (D) may be any compound having an ultraviolet absorbing function, a radical scavenging function, a peroxide decomposition function, or a flame retardant function. Specific examples of the heat stabilizer include phenolic compounds such as hindered phenols, semi-hindered phenols, and less hindered phenols; hindered amines, phosphorus compounds, sulfur compounds, benzotriazoles, benzophenones, hydroxylamines, salicylic acid esters, and triazine compounds. Metal hydrates and halogen compounds may also be used. Known ultraviolet absorbers, antioxidants, and flame retardants may be used. The heat stabilizer (D) may be used alone or in combination of two or more. By including the heat stabilizer (D), the composition may have improved long-term heat resistance and substrate processing suitability. The content of the heat stabilizer (D) when used is, for example, 0.1 to 5% by mass in 100% by mass of the composition excluding the thermally conductive filler (C) and the solvent of the composition.

[0114] Examples of the hindered phenolic compounds include 1,3,5-tris(3,5-di-t-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,1,3-tris-(2'-methyl-4'-hydroxy-5'-t-butylphenyl)-butane, 4,4'-butylidene-bis-(2-t-butyl-5-methylphenol), 3-(3,5-di-t-butyl-4-hydroxyphenyl)stearyl propionate, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 3,9-bis[2-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5.5]Undecane, 1,3,5-tris(3,5-di-t-butyl-4-hydroxyphenylmethyl)-2,4,6-trimethylbenzene, 1,3,5-tris(3-hydroxy-4-t-butyl-2,6-dimethylbenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2,2'-methylenebis(6-t-butyl-4-ethylphenol), 2,2'-thiodiethylbis-(3,5-di- t-Butyl-4-hydroxyphenyl)-propionate, N,N-hexamethylenebis(3,5-di-t-butyl-4-hydroxy-hydrocinnamamide), i-octyl 3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 4,6-bis(dodecylthiomethyl)-o-cresol, calcium salt of 3,5-di-t-butyl-4-hydroxybenzylphosphonic acid monoethyl ester, 4, 6-bis(octylthiomethyl)-o-cresol, bis[3-(3-methyl-4-hydroxy-5-t-butylphenyl)propionic acid]ethylene bisoxybisethylene, 1,6-hexanediol bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 2,4-bis-(n-octylthio)-6-(4-hydroxy-3,5-di-t-butylanilino)-1,3,5-triazine, Examples of such phenols include 2,2'-thio-bis-(6-t-butyl-4-methylphenol), 2,5-di-t-amyl-hydroquinone, 2,6-di-t-butyl-4-nonylphenol, 2,2'-isobutylidene-bis-(4,6-dimethyl-phenol), 2,2'-methylene-bis-(6-(1-methyl-cyclohexyl)-p-cresol), and 2,4-dimethyl-6-(1-methyl-cyclohexyl)-phenol.

[0115] Commercially available products include ADK STAB AO-20, AO-30, AO-40, AO-50, AO-60, AO-80, and AO-330 manufactured by ADEKA CORPORATION; KEMINOX 101, 179, 76, and 9425 manufactured by Chemipro Corporation; IRGANOX 1010, 1035, 1076, 1098, 1135, 1330, 1726, 1425WL, 1520L, 245, 259, 3114, 5057, and 565 manufactured by BASF Corporation; and Cyanox CY-1790 and CY-2777 manufactured by Sun Chemical Corporation.

[0116] Examples of the hindered amine compound include tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)1,2,3,4-butane tetracarboxylate, tetrakis(2,2,6,6-tetramethyl-4-piperidyl)1,2,3,4-butane tetracarboxylate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1-undecanoxy-2,2,6,6-tetramethylpiperidin-4-yl)carbonate, 1,2,2,6,6-pentamethoxy-2,2,6,6-tetramethylpiperidin-4-yl)carbonate, and 1,2,2,6,6-pentamethoxy-2,2,6,6-tetramethylpiperidin-4-yl)carbonate. 2,2,6,6-tetramethyl-4-piperidyl methacrylate, polycondensation product of dimethyl succinate and 1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidine, poly[[6-[(1,1,3,3-tetramethylbutyl)amino]-s-triazine-2,4-diyl]-[(2,2,6,6-tetramethyl-4-piperidyl)imino]-hexamethylene-[(2,2,6,6-tetramethyl-4-piperidyl)imino]], 4-hydroxy-2,2,6,6-tetramethyl-1-pi Ester of peridineethanol with 3,5,5-trimethylhexanoic acid, N,N'-4,7-tetrakis[4,6-bis{N-butyl-N-(1,2,2,6,6-pentamethyl-4-piperidyl)amino}-1,3,5-triazin-2-yl]-4,7-diazadecane-1,10-diamine, decanedioic acid bis(2,2,6,6-tetramethyl-1-(octyloxy)-4-piperidinyl)ester, reaction products of 1,1-dimethylethyl hydroperoxide with octane, bis(1,2,2,6,6-pentamethyl-4-pyridyl)[[3,5-bi 1,2,2,6,6-pentamethyl-4-pyridyl sebacate, poly[[6-morpholino-s-triazine-2,4-diyl]-[(2,2,6,6-tetramethyl-4-piperidyl)imino]-hexamethylene-[(2,2,6,6-tetramethyl-4-piperidyl)imino]], 2,2,6,6-tetramethyl-4-piperidyl-C12-21 and C18 unsaturated fatty acid esters, N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl)-1,6-Hexamethylenediamine, 2-methyl-2-(2,2,6,6-tetramethyl-4-piperidyl)amino-N-(2,2,6,6-tetramethyl-4-piperidyl)propionamide, etc.

[0117] Commercially available products include ADKA STAB LA-52, LA-57, LA-63P, LA-68, LA-72, LA-77Y, LA-77G, LA-81, LA-82, LA-87, LA-402F, and LA-502XP manufactured by ADEKA Corporation; KAMISTAB 29, 62, 77, and 94 manufactured by Chemipro Chemicals; Tinuvin 249, TINUVIN 111FDL, 123, 144, 292, and 5100 manufactured by BASF; and Cyasorb UV-3346, UV-3529, and UV-3853 manufactured by Sun Chemical.

[0118] The phosphorus-based compound is not particularly limited as long as it contains a phosphorus atom, and may be an inorganic compound or an organic compound. Examples of inorganic phosphorus-based compounds include red phosphorus; ammonium phosphates such as monoammonium phosphate, diammonium phosphate, triammonium phosphate, and ammonium polyphosphate; inorganic nitrogen-containing phosphorus compounds such as phosphoric acid amide; phosphoric acid; and phosphine oxide.Examples of organic phosphorus compounds include di(2,6-di-t-butyl-4-methylphenyl)pentaerythritol diphosphite, distearyl pentaerythritol diphosphite, 2,2'-methylenebis(4,6-di-t-butylphenyl)2-ethylhexyl phosphite, tris(2,4-di-t-butylphenyl)phosphite, tris(nonylphenyl)phosphite, tetra(C12-C15 alkyl)-4,4'-isopropylidenediphenyl diphosphite, diphenyl Mono(2-ethylhexyl)phosphite, diphenyl isodecyl phosphite, tris(isodecyl)phosphite, triphenyl phosphite, tetrakis(2,4-di-t-butylphenyl)-4,4-biphenyl diphosphonate, tris(tridecyl)phosphite, phenyl isooctyl phosphite, phenyl isodecyl phosphite, phenyl di(tridecyl)phosphite, diphenyl isooctyl phosphite, diphenyl tridecyl phosphite, 4,4'isopropanol Pyridenediphenol alkyl phosphite, trisnonylphenyl phosphite, trisdinonylphenyl phosphite, tris(biphenyl) phosphite, di(2,4-di-t-butylphenyl)pentaerythritol diphosphite, di(nonylphenyl)pentaerythritol diphosphite, phenyl bisphenol A pentaerythritol diphosphite, tetratridecyl 4,4'-butylidenebis(3-methyl-6-t-butylphenol) diphosphite, hexatride Examples of such phosphite include sil-1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane triphosphite, 3,5-di-t-butyl-4-hydroxybenzyl phosphite diethyl ester, sodium bis(4-t-butylphenyl)phosphite, sodium-2,2-methylene-bis(4,6-di-t-butylphenyl)-phosphite, 1,3-bis(diphenoxyphosphonyloxy)-benzene, and ethyl bis(2,4-ditert-butyl-6-methylphenyl)phosphite.

[0119] Commercially available products include Adeka STAB PEP-36, PEP-8, HP-10, 2112, 1178, 1500, C, 135A, 3010, and TPP manufactured by ADEKA Corporation, IRGAFOS168 manufactured by BASF, HostanoxP-EPQ manufactured by Clariant Chemicals, and HCA manufactured by Sankosha.

[0120] Examples of sulfur-based compounds include 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-(dodecylthio)propionate], ditridecyl 3,3'-thiobispropionate, 2,2-thio-diethylenebis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], 2,4-bis[(octylthio)methyl]-o-cresol, and 2,4-bis[(laurylthio)methyl]-o-cresol.

[0121] Commercially available products include Adeka STAB AO-412S and AO-503 manufactured by ADEKA Corporation, and KEMINOXPLS manufactured by Chemipro Chemicals.

[0122] 1-5.Other optional ingredients The composition may be solvent-free or may contain a solvent, such as toluene, xylene, methyl ethyl ketone, N,N-dimethylformamide, methyl isobutyl ketone, N-methyl-pyrrolidone, acetone, methanol, ethanol, butanol, 2-propanol, 2-methoxyethanol, 2-ethoxyethanol, 1-methoxy-2-propanol, 2-acetoxy-1-methoxypropane, n-hexane, cyclohexane, cyclohexanone, and mixtures thereof.

[0123] From the viewpoint of effectively achieving a low dielectric constant, a fluorine-based filler may be used. Examples of the fluorine-based filler include PTFE, PVDF (vinylidene fluoride polymer having a linear structure in which CF2 and CH2 are alternately bonded), NEOFLON FEP (tetrafluoroethylene-hexafluoropropylene copolymer: tetrafluoroethylene-hexafluoropropylene copolymer resin), PFA (tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer: perfluoroalkoxy resin), NEOFLON ETFE (tetrafluoroethylene and ethylene copolymer), and ECTFE (polychlorotrifluoroethylene: trifluorochloroethylene resin).

[0124] Further, additives may be included within the scope of the present disclosure. For example, a polyimide resin other than the polyimide resin (A) and / or a curable compound other than the curable compound (B) may be used. Any thermoplastic resin may be used. In addition, a catalyst may be included as an optional component to promote the curing process. Suitable examples of the catalyst include imidazole-based, amine-based, and phosphorus-based catalysts. Further, examples of the catalyst include dyes, pigments (e.g., carbon black), polymerization inhibitors, defoamers, leveling agents, ion collectors, moisturizers, viscosity adjusters, preservatives, antibacterial agents, antistatic agents, antiblocking agents, ultraviolet absorbers, infrared absorbers, and electromagnetic wave shielding agents.

[0125] 1-6. Properties of resin composition and cured product The glass transition temperature of the cured product obtained by curing the present composition is set to be in the range of 140 to 400° C., and more preferably 200 to 300° C. When the glass transition temperature is 140° C. or higher, it is possible to enhance long-term heat resistance. On the other hand, when the glass transition temperature is 400° C. or lower, it is possible to impart a certain degree of flexibility and bring out the stress relaxation effect of the polyimide resin (A).

[0126] 2. Manufacturing method of resin composition This composition is obtained by blending each blending component. Instead of a polyimide precursor, an imidized polyimide resin (A) is used as a blending component. A solvent can be used appropriately during blending. The solid content concentration can be, for example, 20 to 60 mass %. Since the polyimide resin (A) has a dimer structure, it can be easily dissolved in various organic solvents.

[0127] The composition can be, for example, in the form of a powder, a film, a sheet, a plate, a pellet, a paste, or a liquid. The liquid or paste resin composition can be easily obtained by adjusting the viscosity using a solvent. The film, sheet, or plate resin composition can be formed, for example, by applying a liquid or paste resin composition and drying it. The powder or pellet resin composition can be obtained, for example, by pulverizing or cutting the film or other resin composition into a desired size.

[0128] 3. Resin composition layer, laminated sheet and prepreg The composition can be suitably used as a resin composition layer. The composition can also be suitably used for laminated sheet applications including a substrate and a resin composition layer formed of the composition on the substrate. The resin composition layer exhibits excellent adhesion after curing treatment, and is therefore suitable for bonding with various materials (resin layers, metal layers, inorganic layers such as ITO, composite layers, etc.). For example, the composition is suitable for use as an adhesive sheet for copper clad laminates (CCL), and as a bonding material between components such as electronic circuit boards and electronic components.

[0129] For example, a coating liquid (varnish) of the present composition containing a solvent is applied to one side of a release film, and the liquid medium such as an organic solvent is removed and dried at, for example, 40 to 150°C, to obtain a laminated sheet having a resin composition layer (adhesive sheet). A laminated sheet that is an adhesive sheet with double-sided release films is obtained by laminating another release film on the surface of the obtained adhesive sheet. By laminating both sides with release films, surface contamination of the adhesive sheet can be prevented. The adhesive sheet can be isolated by peeling off the release film. The two release films can be of the same type or different types. By using release films with different release properties, the peeling force can be made stronger or weaker, making it easier to peel them off in order. In addition, a laminated sheet having an adhesive sheet (resin composition layer) may be obtained by applying the coating liquid to a substrate other than a release substrate.

[0130] Examples of the substrate include resin materials such as polyimide film, polyethylene film, polycarbonate, polyethylene, liquid crystal polymer, phenolic resin, and aramid resin; metal materials such as copper, aluminum, and stainless steel; inorganic materials such as ITO, glass, silicon, and silicon carbide; and composite materials in which these are arbitrarily combined. According to the present composition, the storage modulus G' is 1.0×10 7 The soft polyimide resin (A) having a Pa temperature within the range of −30 to 90° C. not only has excellent adhesion to various substrates but also has excellent moldability.

[0131] The coating method may be selected from known methods such as comma coating, knife coating, die coating, lip coating, roll coating, curtain coating, bar coating, gravure printing, flexographic printing, screen printing, dip coating, spray coating, spin coating, etc. In order to ensure sufficient adhesiveness and from the standpoint of ease of handling, the thickness of the adhesive sheet after drying is preferably 5 to 500 μm, more preferably 10 to 100 μm.

[0132] The present composition can be suitably used for forming a prepreg obtained by impregnating a substrate with the present composition. The prepreg can be produced, for example, by impregnating a fiber substrate with the present composition, and then heating and drying the resin composition to semi-cure (B-stage). The solid content of the resin composition attached to the fiber substrate is preferably 20 to 90 mass% in terms of the content of the resin composition after drying relative to the prepreg. More preferably, it is 30 to 80 mass%, and even more preferably, it is 40 to 70 mass%. For example, the present composition can be impregnated or coated on a fiber substrate so that the solid content of the resin composition in the prepreg is 20 to 90 mass%, and then the prepreg can be produced by heating and drying at a temperature of, for example, 40 to 250°C for 1 to 30 minutes to semi-cure (B-stage).

[0133] As the fiber substrate, known materials can be used without limitation, and examples thereof include organic fibers, inorganic fibers, and glass fibers. Examples of organic fibers include polyimide, polyester, tetrafluoroethylene, and fully aromatic polyamide. Examples of inorganic fibers include carbon fibers. Examples of glass fibers include E-glass cloth, D-glass cloth, S-glass cloth, Q-glass cloth, NE-glass cloth, L-glass cloth, T-glass cloth, spherical glass cloth, and low dielectric glass cloth. Among these, from the viewpoint of low thermal expansion coefficient, E-glass cloth, T-glass cloth, S-glass cloth, Q-glass cloth, and organic fibers are suitable. The fiber substrate may be used alone or in combination of two or more types.

[0134] The shape of the fiber substrate can be appropriately selected depending on the intended use and performance. Specific examples include woven fabric, nonwoven fabric, roving, chopped strand mat, and surfacing mat. Examples of the weaving method of the woven fabric include plain weave, sash weave, and twill weave. It can be arbitrarily selected and designed depending on the desired characteristics. The thickness of the fiber substrate can be, for example, in the range of about 0.01 to 1.0 mm. From the viewpoint of thinning, it is preferably 500 μm or less, more preferably 300 μm or less.

[0135] If necessary, the fiber substrate may be surface-treated with a silane coupling agent or mechanically opened to bring out desired properties. Corona treatment or plasma treatment may also be performed. Surface treatments with silane coupling agents include aminosilane coupling treatment, vinylsilane coupling treatment, cationic silane coupling treatment, and epoxysilane coupling treatment.

[0136] The method of impregnating the fiber substrate with the resin composition is not particularly limited, but examples include a method of preparing a varnish of the resin composition using an organic solvent such as alcohols, ethers, acetals, ketones, esters, alcohol esters, ketone alcohols, ether alcohols, ketone ethers, ketone esters, or ester ethers, and immersing the fiber substrate in the varnish, a method of coating or spraying the varnish onto the fiber substrate, and a method of laminating both sides of the fiber substrate with a film made of the resin composition.

[0137] Furthermore, a resin composition layer formed from the composition is suitable for use as an insulating layer for a semiconductor chip package, an underfill material, an adhesive material, etc. It is also suitable as a composition for copper-clad laminates, a bonding sheet for forming a wiring board, and a cover coat for a flexible substrate.

[0138] 4. Manufacturing method of the cured product A cured product is obtained by curing the composition. When a thermosetting compound is contained, the composition is usually cured by a heat curing process, and when a photocurable compound is contained, the composition is usually cured by a light irradiation process. For example, the resin composition is molded into a desired shape such as a sheet and cured. A molded product such as a sheet of the resin composition can be easily obtained by applying a resin composition containing a solvent and drying it. Then, the molded product is cured to form a cured product. The timing of the molding and the curing may be simultaneous. The sheet-shaped cured product is also called a cured layer.

[0139] The temperature for the heat curing treatment may be appropriately selected depending on the type of the curable compound (B). For example, a method of heat treatment at a temperature of 150 to 300°C for 30 to 180 minutes may be exemplified. In the case of photocuring treatment, active light may be irradiated at an intensity sufficient for curing. During curing, pressure may be applied (for example, 5 MPa) for thermocompression bonding as necessary. A crosslinked structure is formed in the composition by the curing treatment, and a three-dimensionally crosslinked cured product is obtained.

[0140] 5. Cured product and substrate with cured product The cured product obtained from this composition has excellent long-term heat resistance, excellent bending strength, and excellent suitability for substrate processing during the manufacturing process, and is therefore suitable as cured products for various parts such as metal-clad laminates and printed wiring boards, or as cured product-attached substrates containing this cured product. The metal-clad laminate can be obtained, for example, by forming an insulating layer using the present composition, and then laminating the insulating layer and a metal layer. For this insulating layer, an adhesive sheet or a prepreg formed from the present composition can be suitably used. For example, a metal layer and a prepreg formed using the present composition are laminated, and then a curing process is performed by thermocompression to obtain a metal-clad laminate. The thermocompression process can be performed by a known method. For example, the process is performed by hot pressing at a temperature of 120 to 250°C and a pressure of 0.5 to 10 MPa for 0.5 to 5 hours.

[0141] Examples of the laminated structure of the metal-clad laminate include a two-layer laminate of a metal layer / a cured layer, a laminate consisting of a multi-layer of a metal layer / a cured layer / a metal layer, or a multi-layer structure in which a metal layer / a cured layer / a metal layer / a cured layer / a metal layer are alternately laminated. An insulating layer other than the cured layer formed from the present composition may also be included in the laminate. In addition, in order to adjust the thickness of the cured layer, multiple sheets of prepreg or the like may be stacked and cured. In addition, a conductive layer other than the metal layer may be laminated.

[0142] For example, a metal-clad laminate having a layer structure of metal layer / hardened layer / metal layer can be obtained by forming a circuit pattern on the metal layer formed on both main surfaces of the hardened layer to obtain a circuit board having a circuit pattern layer. A through hole or via may be formed in the hardened layer by a laser or the like. A core board may be laminated with an insulating hardened layer by a build-up process to form a via and to form a multi-layer structure. The circuit board can be obtained, for example, by forming the metal layer of the metal-clad laminate into a desired circuit pattern by a subtractive method, or by forming a desired circuit pattern on one or both sides of the insulating layer by an additive method.

[0143] Copper foil or the like is used as the metal layer. In the case of a copper-clad laminate, a step is performed in which electrolytic copper plating is performed on the copper foil surface, and then etching is performed with an alkaline or other plating solution after removing the resist layer. The present composition is suitable for use in copper-clad laminates because it has excellent substrate processing suitability such as plating solution resistance. Furthermore, the present cured product has excellent bending strength and long-term heat resistance, so that a substrate with the cured product, including the cured product formed by curing the present composition, can be used for a wide range of applications under various environments.

[0144] The printed wiring board can be manufactured, for example, by processing the copper foil in a copper-clad laminate by etching or the like, forming a signal circuit or the like, bonding the obtained substrate and cover film via an adhesive sheet, and carrying out a curing process or the like. In addition, for example, a flexible printed wiring board can be manufactured by forming a conductor pattern on an insulating flexible film, forming a protective film thereon via the adhesive sheet, and carrying out a process of thermocompression bonding or the like. Examples of the flexible film include polyester, polyimide, liquid crystal polymer, and PTFE films. Examples of the conductor pattern include a method of forming the conductor pattern by a printing technique, and a method of sputtering or plating.

[0145] The cured layer of the composition formed on one or both sides of the printed wiring board may be provided with an opening by drilling or laser processing, and filled with a conductive agent to form a via. A circuit layer may also be formed on the cured layer of the composition. The cured product of the composition has excellent plating resistance, and is therefore suitable for the manufacture of multi-layer printed wiring boards. The printed wiring board formed using the composition has excellent processability and excellent long-term heat resistance and bending strength, and is therefore suitable for various electronic devices such as smartphones and tablet terminals.

[0146] Since the polyimide resin (A) of the composition has excellent electrical insulation, a cured product having excellent insulation can be provided by using an insulating material for the curable compound (B) or the thermally conductive filler (C). For example, it is preferably used as an insulating layer forming material on a circuit board (including a coverlay layer of a printed wiring board, an interlayer insulating layer of a built-up board, a bonding sheet, etc.). In addition, by using a conductive material in a filler such as the thermally conductive filler (C), it can also be used as a conductive member of an electronic component. Examples of electronic components include power modules such as power semiconductor devices, LEDs, and inverter devices.

[0147] Furthermore, since the cured product of the present composition contains a thermally conductive filler (C), it can be applied to all applications requiring heat dissipation. For example, by utilizing the moldability of the resin composition, it can be suitably used as a heat dissipation part of a desired shape. In particular, it is useful as a heat dissipation adhesive or heat dissipation sheet for electronic devices (smartphones, tablet terminals, etc.) that cannot be equipped with fans or heat sinks due to the need for light, thin, short, and small size, and for battery exterior materials, because of the need for heat dissipation adhesive or heat dissipation sheet for battery exterior materials. In addition, the cured product of the present composition is suitable as an adhesive layer between a heating element and a heat sink, or as a heat spreader. In addition, it can be applied as a heat dissipation layer that covers one or more electronic components mounted on a substrate. EXAMPLES

[0148] The present disclosure will be described in more detail below with reference to examples. The present disclosure is not limited to the following examples. Unless otherwise specified, "%" and "parts" are based on mass.

[0149] (i) Measurement of weight average molecular weight (Mw) The Mw was measured using a Showa Denko GPC (gel permeation chromatograph) "GPC-101". The solvent was THF (tetrahydrofuran), and two "KF-805L" (Showa Denko GPC column: 8 mm ID x 300 mm size) connected in series were used as the column. The conditions were sample concentration 1 mass%, flow rate 1.0 mL / min, pressure 3.8 MPa, column temperature 40°C, and Mw was determined in polystyrene equivalent. Data analysis was performed using the manufacturer's built-in software to calculate the calibration curve, molecular weight, and peak area, and Mw was calculated for the range of retention times from 17.9 to 30.0 minutes.

[0150] (ii) Acid value measurement The acid value was measured in accordance with JIS K0070. Specifically, about 1 g of sample (polyimide resin (A)) was precisely weighed and placed in a stoppered Erlenmeyer flask, and 100 mL of cyclohexanone solvent was added to dissolve it. Phenolphthalein test solution was added as an indicator, and titration was performed with 0.1N alcoholic potassium hydroxide solution. The end point was when the indicator retained a pale pink color for 30 seconds. The acid value was calculated using the following formula. Acid value (mgKOH / g)=(5.611×a×F) / S however, S: Amount of sample collected (g) a: Consumption of 0.1N alcoholic potassium hydroxide solution (mL) F: Potency of 0.1N alcoholic potassium hydroxide solution

[0151] (iii) Measurement of phenolic hydroxyl value The phenolic hydroxyl value was measured according to JIS K0070. The phenolic hydroxyl value is expressed as the amount (mg) of potassium hydroxide required to neutralize the acetic acid bonded to the phenolic hydroxyl group when the phenolic hydroxyl group contained in 1 g of polyimide resin (A) is acetylated. The phenolic hydroxyl value of polyimide resin (A) was calculated taking into account the acid value as shown in the following formula. Specifically, about 1 g of sample (polyimide resin (A)) was precisely weighed and taken into a stoppered Erlenmeyer flask, and 100 mL of cyclohexanone solvent was added to dissolve it. Furthermore, exactly 5 mL of an acetylating agent (a solution in which 25 g of acetic anhydride was dissolved in pyridine to a volume of 100 mL) was added and stirred for about 1 hour. Phenolphthalein test solution was added as an indicator to this and held for 30 seconds. Then, the solution was titrated with 0.5 N alcoholic potassium hydroxide solution until it turned a light pink color. The phenolic hydroxyl value was calculated according to the following formula. Phenolic hydroxyl value (mgKOH / g) = [{(ba) × F × 28.05} / S] + D however, S: Amount of sample collected (g) a: Consumption of 0.5N alcoholic potassium hydroxide solution (mL) b: Amount of 0.5N alcoholic potassium hydroxide solution consumed in the blank experiment (mL) F: Potency of 0.5N alcoholic potassium hydroxide solution D: Acid value (mgKOH / g) The value of b can be determined by titrating 5 mL of the acetylating agent (a 100 mL solution of 25 g of acetic anhydride dissolved in pyridine) with a 0.5 N alcoholic potassium hydroxide solution.

[0152] (iv) Determination of acid anhydride value Approximately 1 g of sample (polyimide resin (A)) was precisely weighed and placed in a stoppered Erlenmeyer flask, and 100 mL of 1,4-dioxane solvent was added to dissolve it. 10 mL of a mixed solution of octylamine, 1,4-dioxane, and water (mixing ratio (mass) 1.49 / 800 / 80) in which the amount of acid anhydride groups in the sample was greater than the amount of acid anhydride groups in the sample was added and stirred for 15 minutes to react with the acid anhydride groups. The excess octylamine was then titrated with a mixed solution of 0.02 M perchloric acid and 1,4-dioxane. In addition, a blank measurement was also performed using 10 mL of a mixed solution of octylamine, 1,4-dioxane, and water (mixing ratio (mass) 1.49 / 800 / 80) to which no sample had been added. The acid anhydride group value was calculated using the following formula (unit: mgKOH / g): Acid anhydride value (mgKOH / g) = 0.02 x (BA) x F x 56.11 / S B: Blank titration volume (mL) A: titration volume of sample (mL) S: Amount of sample collected (g) F: Potency of 0.02 mol / L perchloric acid

[0153] (v) Amine value determination Approximately 1 g of sample (polyimide resin (A)) is precisely weighed and placed in a stoppered Erlenmeyer flask, and 100 mL of cyclohexanone solvent is added to dissolve. A few drops of indicator, which is prepared by mixing 0.20 g of Methyl Orange dissolved in 50 mL of distilled water and 0.28 g of Xylene Cyanol FF dissolved in 50 mL of methanol, are added and held for 30 seconds. The solution is then titrated with 0.1 N alcoholic hydrochloric acid solution until it turns blue-gray. The amine value is calculated using the following formula: Amine number (mgKOH / g) = (5.611 x a x F) / S however, S: Amount of sample collected (g) a: Consumption of 0.1N alcoholic hydrochloric acid solution (mL) F: Potency of 0.1N alcoholic hydrochloric acid solution

[0154] (vi) Storage modulus G' is 1.0 × 10 7 Measurement of temperature at which Pa is reached A coating solution in which the polyimide resin (A) according to each synthesis example was dissolved in cyclohexanone to a non-volatile content of 35% was applied onto a heat-resistant release film using a doctor blade with a gap of 10 mil, and a resin sheet having a thickness of 25 μm was obtained by drying for 10 minutes at 130° C. The resin sheet obtained was peeled off from the heavy release film, and the storage modulus and Tg of the resin sheet were measured using a dynamic viscoelasticity measuring device "DVA200" (manufactured by IT Measurement and Control Co., Ltd.). The storage modulus was measured by cooling the resin sheet to 0°C, then raising the temperature to 300°C at a rate of 10°C / min, measuring the viscoelasticity at a vibration frequency of 10 Hz and a grip length of 10 mm, and determining whether the storage modulus G' was 1.0×10 7 The temperature at which the temperature reached 1 Pa was confirmed. Heating rate: 10℃ / min Measurement frequency: 10Hz Grip length: 10mm Width: 5mm

[0155] <Synthesis of polyimide resin> [Synthesis Example 1] In a 1L separable flask equipped with an oil bath and a stirring rod, 200g of cyclohexanone was added while introducing nitrogen gas, 149.4g of dimer diamine (PRIAMINE1075) as a diamine, 4.7g of m-aminophenol as a monoamine compound were added while stirring, and then 67.3g of 1,2,4,5-cyclohexanetetracarboxylic dianhydride as a tetracarboxylic acid was added and stirred at room temperature for 30 minutes. The mixture was heated to 100°C and stirred for 3 hours, after which the oil bath was removed and the temperature was returned to room temperature to obtain a varnish-like polyimide precursor. The mixture was then heated at 170°C for 10 hours while removing the distilled water from the system using a Dean-Stark trap, and imidized to obtain polyimide resin P1.

[0156] [Synthesis Examples 2 to 32, Comparative Synthesis Examples 1 to 8] Polyimide resins P2 to P32 and N1 to N8 were obtained in the same manner as in Synthesis Example 1, except that the monomers and their amounts were changed as shown in Tables 1 to 4. The abbreviations in Tables 1 to 4 are as follows. DM1: 1,2,4,5-cyclohexanetetracarboxylic dianhydride DM2: 1,2,3,4-butanetetracarboxylic dianhydride DM3: 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride DM4: 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride DM5: 5-(2,5-dioxotetrahydrofuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride DM6: X-22-168B (Shin-Etsu Chemical Co., Ltd., siloxane-type tetracarboxylic dianhydride, molecular weight 2960) MM1: Maleic anhydride MM2: Phthalic anhydride DA1: Priamine 1075 (dimer diamine, manufactured by Croda Japan) DA2: 4,4'-(hexafluoroisopropylidene)bis(2-aminophenol) DA3: 1,12-dodecanediamine DA4: KF-8010 (Shin-Etsu Chemical Co., Ltd., siloxane diamine, molecular weight 850) DA5: D-2000 (HUNTSMAN, polypropylene glycol type polyether diamine, molecular weight 2000) MA1: m-aminophenol MA2: o-aminophenol MA3: p-aminophenol MA4: 4-hydroxyphenethylamine (tyramine) MA5:1-Aminodecane

[0157] Tables 1 to 4 show the blending amounts (parts by mass), the phenolic hydroxyl group (PhOH) value, acid anhydride group value, amine value, maleimide value, and total functional group value of the obtained polyimide resin. 1 X for 100 mol% of residues 1 Mole % of a residues, X 2 X for 100 mol% of residues 2The mol% of the d residue is shown. The Mw and storage modulus G' of the polyimide resin (A) are 1.0×10 7 The temperature at which the viscosity becomes 1 Pa and the average total number of functional groups selected from amino groups, acid anhydride groups, and maleimide groups in the polyimide resin (A) are shown. The maleimide value was calculated from the amount of polyimide resin (A) used in the synthesis. In this example, the total functional value is the total functional value of the phenolic hydroxyl value + acid anhydride value + amine value + maleimide value. When a carboxyl group is contained, the carboxyl value may be added to the above formula.

[0158] [Table 1]

[0159] [Table 2]

[0160] [Table 3]

[0161] [Table 4]

[0162] [Example 1] <<Preparation of resin composition (varnish)>> A container was charged with 100 parts of the polyimide resin (P1) of Synthesis Example 1 in terms of solid content, 80 parts each of (B)-1 and (B)-2 as the curable compounds (B), and 260 parts of the thermally conductive filler (C)-1, and a mixed solvent (toluene:MEK=9:1 (mass ratio)) was added so that the non-volatile component concentration was 50%, and the mixture was stirred for 10 minutes with a disper to obtain a varnish of Example 1.

[0163] <<Prepreg Manufacturing 1>> Next, the obtained varnish was impregnated into a glass cloth (Nitto Boseki Co., Ltd., #2116 type, WEA116E, E glass) so that the mass ratio of glass cloth:resin composition of non-volatile components was 2:3, and then the prepreg 1 of Example 1 was obtained by heating and drying at 140°C for about 5 minutes.

[0164] <<Prepreg Manufacturing 2>> Prepreg 2 according to Example 1 was obtained in the same manner as in Prepreg Production 1, except that the heating and drying temperature and time were changed to 120° C.×5 minutes.

[0165] <Manufacturing of copper-clad laminates> The obtained prepreg 1 and 35 μm thick copper foil were laminated in three layers each, and hot pressed under conditions of 250° C., 3.0 MPa, and 120 minutes, and finally, 35 μm thick copper foil was arranged on the outermost layers on both sides to obtain a copper-clad laminate according to Example 1. Then, the evaluation described below was performed. The results are shown in Table 5.

[0166] [Examples 2 to 55, Comparative Examples 1 to 15] Except for changing the ingredients and amounts as shown in Tables 5 to 9, varnishes according to Examples 2 to 48, 50 to 53 and Comparative Examples 1 to 15 were prepared in the same manner as in Example 1, and prepreg 1 and prepreg 2 were obtained. For Examples 49, 54, and 55, instead of prepreg 1, an adhesive sheet which was a resin composition layer obtained in <<Production of adhesive sheet>> described below was used to obtain a copper-clad laminate in the same manner. The evaluation results are shown in Tables 4 to 9.

[0167] <<Manufacture of adhesive sheets, etc.>> The varnishes of Examples 49, 54, and 55 were uniformly coated on a 50 μm thick heavy release film (polyethylene terephthalate (PET) film coated with a heavy release agent) using a doctor blade so that the thickness after drying was 50 μm, and then dried at 100 ° C for 2 minutes. After that, it was cooled to room temperature to obtain an adhesive sheet with a single-sided release film. Next, the adhesive sheet surface of the obtained adhesive sheet with a single-sided release film was superimposed on a 50 μm thick light release film (PET film coated with a light release agent) to obtain a laminated sheet with a double-sided release film consisting of a heavy release film / adhesive sheet / light release film. The obtained adhesive sheet and 35 μm thick copper foil were laminated in three layers each, and hot pressed under conditions of 250 ° C, 3.0 MPa, and 120 minutes, and finally, a copper foil with a thickness of 35 μm was placed on the outermost layers on both sides to obtain a copper-clad laminate.

[0168] The materials used in the examples and comparative examples are shown below. (Curable compound (B)) (B)-1: Epoxy compound (b1), XD-1000 (manufactured by Nippon Kayaku Co., Ltd., dicyclopentadiene type epoxy, multifunctional, functional group equivalent 252 g / eq.) (B)-2: Cyanate ester compound (b2), BAD (manufactured by Mitsubishi Gas Chemical Company, bisphenol A type cyanate ester, bifunctional, functional group equivalent 139 g / eq) (B)-3: Maleimide compound (b3), BMI-3000 (manufactured by Daiwa Chemical Industry Co., Ltd., bisphenol A diphenyl ether bismaleimide, bifunctional, functional group equivalent 285.3 g / eq.) (B)-4: Polyphenylene ether compound (b4), Noryl (registered trademark) SA9000 (SABIC, methacrylate group-containing polyphenylene ether, bifunctional, functional group equivalent: 850 g / eq.) (B)-5: Nadimide compound (b5), BANI-M (manufactured by Maruzen Petrochemical Co., Ltd., bisallylnadimide, bifunctional) (B)-6: Active ester compound, HPC-8000-65T (SABIC, active ester compound) (B)-7: Phenol resin, H-4 (manufactured by Meiwa Kasei Co., Ltd.) (B)-8: Dodecanedioic acid dihydrazide (Thermal conductive filler (C)) (C)-1: AO-509 (Admatechs, alumina) (C)-2: SP-2 (Denka, boron nitride) (C)-3: SC2050-MB (Admatechs, silica) (C)-4: FZO-50 (Ishihara Sangyo Kaisha, zinc oxide) (Heat stabilizer (D)) (D)-1:2 Pentaerythrityl-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] (BASF "IRGANOX1010") (D)-2: TT-LX (1-[N,N-bis(2-ethylhexyl)aminomethyl]methylbenzotriazole) (D)-3: Bis(2-arylphenoxy)phosphazene

[0169] (vii) Measurement of Tg of cured resin composition The varnish according to each example was applied onto a heat-resistant release film using a doctor blade with a gap of 10 mil, and dried at 130°C for 10 min to obtain a resin composition layer having a thickness of 25 μm. The obtained resin composition layer was peeled off from the heavy release film and heat-treated at 250°C for 60 minutes to obtain a cured layer. The loss tangent (tan δ) of the obtained cured layer was measured in the temperature range of -50 to 400°C using a dynamic viscoelasticity measuring device similar to that in (vi) under the same conditions of heating rate, measurement frequency, grip length, and width, and Tg was measured by the same method as above.

[0170] α. Bending strength The obtained copper-clad laminate was cut into a width of 40 mm and a length of 25 mm, and the outermost copper foil on both sides of the cut copper-clad laminate was removed to prepare a test piece. On a plane parallel to the horizontal plane, two supporting members made of metal and having rounded ends were arranged at an interval (23.7 mm) shorter than the length of the test piece. The test piece was arranged on the supporting members so that the center of the test piece in the longitudinal direction overlapped with the center of the interval between the two supporting members. Next, a pressing tool made of metal and having rounded ends was pressed against the center of the test piece from above the center of the test piece to apply force to the test piece. The speed at which force was applied to the test piece was 1.0 mm / min. The test piece was continued to be subjected to force, and the test was terminated when the test piece broke. The bending strength converted to a thickness of 1.6 mm was calculated based on the distance between the supporting members (distance between the fulcrums), the width of the test piece, the thickness of the test piece, and the force applied when the test piece broke. A: 400N / mm 2 The end. B: 300N / mm 2 More than 400N / mm 2 less than. C: 200N / mm 2 More than 300N / mm 2 less than. D: 150N / mm 2 More than 200N / mm 2 less than. E: 100N / mm 2 More than 150N / mm 2 less than. F: 100N / mm 2 Less than. Not practical.

[0171] β. Circuit board processing suitability A printed wiring board for evaluation was prepared according to the following method, and a series of tests were carried out for embeddability, heat cycle resistance, and plating solution resistance. After that, the printed wiring board for evaluation was cut, and the exposed cross section was observed under an optical microscope at 100x magnification.

[0172] <Preparation of printed wiring board for evaluation (embedding test into copper circuit)> A glass cloth-based epoxy resin copper-clad laminate with two circuit patterns, L / S=25μm / 25μm and copper thickness of 25μm and 50μm, was prepared as an inner layer circuit board. On both sides of the board, prepregs according to the examples and comparative examples (hereinafter referred to as each example) were hot-pressed at 250℃, 3.0MPa, and 120 minutes, and then copper foil was placed on the outermost layers on both sides to obtain a printed wiring board for evaluation. In Examples 49, 54, and 55, the adhesive sheets obtained were used to obtain printed wiring boards for evaluation in the same manner.

[0173] <Heat cycle test> The above-mentioned printed wiring board for evaluation was placed in a thermal shock device ("TSE-11-A", manufactured by Espec Corporation) and subjected to alternating exposure a prescribed number of times under the following conditions: high temperature exposure: 125°C, 15 minutes; low temperature exposure: -50°C, 15 minutes.

[0174] <Plating solution resistance test> After the heat cycle test, the evaluation printed wiring board was subjected to the acid plating test described below, and then washed with pure water and dried. The same sample was then subjected to the alkaline plating test described below. [I. Acid plating test] The adhesive sheet with double-sided release film was cut to a size of 65 mm x 65 mm, and the light release film was peeled off. The adhesive sheet surface exposed by peeling was laminated at 90 ° C with two layers of CCL [ESPANEX MC18-25-00FRM] copper surface manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., and then pressure-bonded for 60 minutes under conditions of 180 ° C and 2.0 MPa. Finally, the heavy release film was peeled off to prepare a test piece for evaluation. The light release film was peeled off from the adhesive sheet with double-sided release film for this test piece, and the exposed adhesive sheet surface was subjected to electroless nickel treatment according to the following procedures and conditions h to n. h. Acidic degreasing process: Immerse in ICP Clean S-135K (manufactured by Okuno Chemical Industries Co., Ltd.) at 40°C for 4 minutes. i. Soft etching step: Immersion in sodium persulfate at 30°C for 1 minute. j. Desmutting process: Immerse in sulfuric acid at 25°C for 1 minute. k. Pre-dip process: Immerse in 25°C hydrochloric acid for 30 seconds. l. Activation process: Immerse in ICP Accela (manufactured by Okuno Chemical Industries Co., Ltd.) at 30°C for 1 minute. m. Post-dip step: Immerse in sulfuric acid at 25°C for 1 minute. n. Electroless nickel plating process: Immerse in IP Nicoron FPF (manufactured by Okuno Chemical Industries Co., Ltd.) at 85°C for 20 minutes. [II. Alkaline plating test] Test pieces for evaluation were prepared in the same manner as in the acid plating test, and electroless nickel treatment was performed on these test pieces according to the procedures and conditions s to w described below. s. Alkaline degreasing process: Immersion in an alkaline degreasing agent (50 g / L aqueous solution of Ace Clean A-220 (trade name) manufactured by Okuno Chemical Industries Co., Ltd.) at 50°C for 5 minutes. t. Etching treatment step: Immersion in an aqueous solution containing 400 g / L of chromic anhydride and 400 g / L of 98% sulfuric acid at 67°C for 10 minutes. u. Activation step: Immerse in an aqueous solution containing 20 mL / L of 98% sulfuric acid at 25°C for 2 minutes. v. Catalytic activation: Immersed in a catalyst activation solution (aqueous solution containing 10 mL / L of TSP Activator Concentrate (trademark), manufactured by Okuno Chemical Industries Co., Ltd.) at 25°C for 2 minutes. w. Electroless nickel plating process: Immerse in an ammonia-alkali type autocatalytic electroless nickel plating solution (manufactured by Okuno Chemical Industries, a pH 9 aqueous solution containing 160 mL / L of Chemical Nickel A (trade name) and 160 mL / L of Chemical Nickel B (trade name)) at 40°C for 5 minutes.

[0175] The samples subjected to the above series of tests were evaluated according to the following criteria: "Poor appearance" refers to peeling from the substrate surface, generation of voids, etc. A: No defects were observed in appearance after embedding tests into 50μm-thick copper circuits, 5000 heat cycle tests, and plating solution resistance tests. B: Not applicable to A above, but no defects in appearance were found after embedding in a 50 μm thick copper circuit, 1000 heat cycle tests, and plating solution resistance tests. C: Not applicable to A or B above, but no defects in appearance after embedding test in 50 μm thick copper circuit, 200 heat cycle test, and plating solution resistance test. D: Not applicable to A to C above, but no defects in appearance were observed after embedding test in 25 μm thick copper circuit, 200 heat cycle test, and plating solution resistance test. E: Not applicable to A to D above, but no defects in appearance were observed after the embedding test in a 25 μm-thick copper circuit, the 50-time heat cycle test, and the plating solution resistance test. F: Does not fall under any of the above A to E. Not practical.

[0176] γ.Long-term heat resistance The prepreg or adhesive sheet prepared in each example was cut into a width of 40 mm and a length of 25 mm, and the cut sample was hot-pressed at 250°C, 3.0 MPa, and 120 minutes to obtain a cured product, and the initial Tg was measured. The cured product was then stored in a hot air oven in an air atmosphere at 250°C for 1000 hours, and the Tg after storage was measured. The long-term heat resistance was evaluated from the decrease in Tg after storage compared to the Tg before storage. A: The decrease is less than 5%. B: Decrease rate is 5% or more but less than 8%. C: Decrease rate is 8% or more but less than 10%. D: Decrease is 10% or more but less than 15%. E: Decrease is 15% or more but less than 20%. F: Reduction of 20% or more. Not practical.

[0177] δ. Fabrication of prepregs 1 and 2 Prepregs 1 and 2 of each example were cut, and the exposed cross sections were observed with a scanning electron microscope (SEM) at a magnification of 5000. Note that the term "void" refers to a crack having a size of 0.1 μm or more. A: No voids were observed when dried at 120°C for about 5 minutes or at 140°C for about 5 minutes. B: When dried at 120°C for about 5 minutes, voids were observed, but when dried at 140°C for about 5 minutes, no voids were observed.

[0178] [Table 5]

[0179] [Table 6]

[0180] [Table 7]

[0181] [Table 8]

[0182] [Table 9]

[0183] Resin compositions containing polyimide resins having an average total number of functional groups per molecule that is greater than 1, including amino groups, acid anhydride groups, and maleimide groups, were poor in suitability for substrate processing, as shown in Comparative Examples 1 to 3. In addition, the storage modulus G' was 1.0×10 7 Resin compositions using polyimide resins with a temperature exceeding 90°C at which the molecular weight becomes Pa were inferior in bending strength as shown in Comparative Examples 4 and 5. In addition, resin compositions using polyimide resins with Mw less than 10,000 were inferior in substrate processability as shown in Comparative Example 6. Furthermore, resin compositions using polyimide resins with Mw exceeding 100,000 were inferior in long-term heat resistance as shown in Comparative Example 7. On the other hand, it was confirmed that Examples 1 to 55 according to the present disclosure have substrate processability that combines embedding ability into substrate irregularities, heat cycle resistance, and plating solution resistance, and that the cured products thereof have excellent long-term heat resistance and bending strength.

[0184] This application claims priority based on Japanese Patent Application No. 2021-213179, filed on December 27, 2021, the disclosure of which is incorporated herein in its entirety.

Claims

1. A resin composition comprising a polyimide resin (A), a curable compound (B) and a thermally conductive filler (C), The polyimide resin (A) contains a residue X derived from dimer diamine and / or dimer diisocyanate. 2 d, the total average number of functional groups selected from an amino group, an acid anhydride group and a maleimide group is 1 or less, inclusive of 0, The storage modulus G' of the polyimide resin (A) is 1.0×10 7 the temperature at which the viscosity of the polyimide resin (A) becomes 0.02 Pa is either −30° C. or higher or lower than 30° C., and the weight average molecular weight of the polyimide resin (A) is 10,000 to 100,000; the curable compound (B) is one or more selected from the group consisting of an epoxy compound (b1), a cyanate ester compound (b2), a maleimide compound (b3), a polyphenylene ether compound (b4) and a nadimide compound (b5); A resin composition having a glass transition temperature of 140 to 400°C after curing.

2. The polyimide resin (A) is represented by the general formula (1): [Formula 1] (X 1 is independently a tetravalent tetracarboxylic acid residue for each repeating unit, and X 2 is a divalent organic group for each repeating unit, 1 and imide bonds are bonded together to form two imide rings.) The repeating unit has a structure represented by The X constituting the polyimide resin (A) 2 When the whole is taken as 100 mol %, the residue X derived from the dimer diamine and / or dimer diisocyanate is 2 2. The resin composition according to claim 1, wherein d is 60 to 100 mol %.

3. The resin composition according to claim 1, further comprising a heat stabilizer (D).

4. 2. The resin composition according to claim 1, wherein the polyimide resin (A) is blended in an amount of 1 to 40% by mass based on 100% by mass of non-volatile components of the resin composition.

5. 2. The resin composition according to claim 1, comprising an epoxy compound (b1) as the curable compound (B) and further comprising an active ester compound.

6. A laminate sheet comprising a substrate and a resin composition layer formed on the substrate using the resin composition according to any one of claims 1 to 5.

7. A prepreg comprising a substrate impregnated with the resin composition according to any one of claims 1 to 5.

8. A cured product obtained from the resin composition according to any one of claims 1 to 5.

9. A substrate having a cured product formed by curing the resin composition according to any one of claims 1 to 5.

10. An electronic device equipped with the substrate with the cured product according to claim 9.

Citation Information

Patent Citations

  • Information recorder

    JP1988091851A

  • Polyimide-based adhesive composition, cured product, adhesive sheet, laminate, and flexible printed board

    JP2013199645A

  • Functionalized polyimide resin and epoxy resin composition including the same

    JP2015117278A

  • Polyimide-based adhesive, film adhesive, adhesive layer, adhesive sheet, copper-clad laminate and printed wiring board, and multi-layer wiring board and its manufacturing method

    JP2016191049A

  • Diamine compound as polyimide raw material for forming photoelectric display device, polyamide acid and polyimide using the same

    JP2019119755A